Genome sequencing reveals genes under selection for olfactory transduction in highland sheep - Anees Ahmad; Muhammad Ibrahim; Muhammad Yaqoob; Muhammad Fahim; Sher Hayat Khan; Israr Ud Din; Majid Khan; Sohail Ahmad (Molecular Genetics and Genomics, 2026)
Kutta is an indigenous sheep breed found in the mountainous region of Swat, Pakistan. In this study we evaluated the performance of Kutta sheep within their natural habitat and identified genomic regions associated with environmental adaptability using whole genome sequencing. Flocks are mostly managed under a transhumant production system with year-round breeding. Kutta sheep demonstrated higher lambing efficiency under the available resources. Although the body size of rams and ewes was comparable, significant variation was observed among different age groups. Whole genome sequencing identified 15.46 million variants relative to Oar_v1.0 reference genome assembly. Exonic variants accounted for 2.3% of all protein coding gene variants and affected 6347 genes. These genes were primarily enriched in pathways related to G protein-coupled receptor signaling (700 genes) and olfactory transduction (500 genes). Selective sweep analysis detected 1930 genes within the regions of high homozygosity across the genome. Based on homozygosity patterns, biological relevance, and colocalization with known QTLs, 11 candidate genes were identified as putative selective signature. Five of these genes (OR4C6L, OR1086L, OR5AK2L, QR5T2L, OR9Q2) belonged to the olfactory receptor family. These olfactory receptor genes may contribute to high-altitude adaptation in Kutta sheep by enhancing their ability to locate food resources, recognize mates, and detect predators in challenging mountainous environments. Further screening of the OR4C6L sequence across 12 indigenous sheep breeds revealed marked differences between highland and lowland populations. Collectively, these findings provide comprehensive genomic insights into high-altitude adaptation of sheep and highlight the potential role of olfactory perception in survival and environmental fitness.

Genome-wide characterization and comparative analysis of Bacillus paranthracis MBBL1 reveals genomic plasticity features - Nimra Hanif; Muhammad Naveed; Maida Salah Ud Din; Tariq Aziz; Ashwag Shami; Fakhria A. Al-Joufi (Functional & Integrative Genomics, 2026)

Genomic characterization of genes controlling stay-green trait in bread wheat - Alia Anwar; Xingguo Ye; Hafiz Sabah-Ud-Din Mazhar; Muhammad Waleed Meeran; Ralf Müller-Xing; Muhammad Ashfaq; Muhammad Arshad Javed; Javaria Tabassum; Umar Masood Quraishi; Farheen Solangi; Shajiha Naeem (Euphytica, 2026)

Can host genetics transform the sustainable control of tropical theileriosis? Insights from the Tick-Theileria interface - Abdullah Azeem; Muhammad Kasib Khan; Muhammad Shahid Mahmood; Rao Zahid Abbas; Muhammad Umer Ashraf; Sultan Ali; Muhammad Adnan Sabir Mughal; Zaheer Abbas; Sundas Afresham; Mehroz Latif; Muhammad Imran; Zia ud Din Sindhu (Veterinary Parasitology, 2026)

Influence of tea-derived polyphenols architecture on the structural, functional and allergenicity properties of β-lactoglobulin: A comparison of non-covalent and covalent interactions - Zhi-Wei Liu; Jia-Wei Zou; Xiu-Bin Liu; Waqar Ahmed; Rana Muhammad Aadil; Marwa Ezz El-Din Ibrahim; Jun-Hu Cheng; Xie-Ling He; Hou-Gang Zhou; Hong-Ying Guo (Food Research International, 2026)

Contamination levels, eco-health risks, and source identification of some potentially toxic elements in roadside dust along the Indus Highway (N-55), Pakistan using compositional data analysis - Amanullah; Wajid Ali; Saad Khan; Said Muhammad; Abdur Raziq; Muhamamd Nafees; Imran Ud Din (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Correction: Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2026)

Etiology and integrated management of fruit rot of peach (Prunus persica L.) caused by a mycotoxigenic Aspergillus flavus - Palwasha; Siraj ud Din; Muhammad Fahim (European Journal of Plant Pathology, 2026)

Removal of arsenic from aqueous solution using a surface-functionalized magnetic biochar derived from Chlorella - Muhammad Irfan; Israr Masood ul Hasan; Muhammad Jafir; Chang Li; Jie Hu; Muhammad Moeen ud din; Khalid Hussain; Yixing Zhu; Liugen Zheng (Marine Pollution Bulletin, 2026)

The Role of Biochar in Boosting Soil Microbial Diversity, Metabolic Activity, and Heavy Metal Retention in Rice Agroecosystems - Ihsan ud din; Liangfang Ma; Xiyu Tan; Yihang Chen; Qihua Liang; Muhammad Afzal; Zhiyuan Tan (Water, Air, & Soil Pollution, 2026)

Impact of Various Global Digital Elevation and Crustal Density Models on Accurate Topographic Correction for Geoid Modelling Over East Malaysia - Noorhurul Ain Othman; Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Mohamad Azril Che Aziz; Chivatsi Jonathan Nyoka; Nurul Shafiqah Hazelin Noor Azmin; Afreena Nisha Mohd Zamri (Pure and Applied Geophysics, 2026)

Genotypic Characterization of Genetic Diversity for the Development of Leaf Rust Resistance in Bread Wheat using SSR Markers - Mueen Alam Khan; Muhammad Farooq Naseer; Jafarov Valeh; Hafiz Ghulam Muhu Din Ahmed; Beena Alam; Adel A. Rezk; Nora M. Al Aboud (Plant Molecular Biology Reporter, 2026)

Machine learning-assisted meta-analysis reveals melatonin crosstalk regulating plant growth plasticity under heavy metal stress - Muhammad Moeen-ud-din; Muhammad Azher Hassan; Ambreen Ahmad; Liu Xianhua; Muhammad Ishfaq; Muhammad Irfan; Yujiang Li; Liu Yang; Liu Chunguang (Plant Cell Reports, 2026)

In silico evaluation of protocatechuate 4,5-dioxygenase for environmental detoxification of persistent organic pollutants - Muhammad Naveed; Maryum Rasheed; Maida Salah Ud Din; Minahil Zahid; Ayaz Ali Khan; Mayasar I. Al Zaban; Ashwag Shami; Hayam A. Alwabsi (Biodegradation, 2026)

Slow-Release DAP Fertilizer Coated with Bacillus velezensis FB2 and Polyvinyl Alcohol for Sustainable Maize Production - Zumrah Rehman; Muhammad Bilal Khan Niazi; Zaib Jahan; Ghulam Abbas Shah; Hazrat Ali; Zia Ur Rahman Farooqi; Waqas Mohy-Ud-Din; Qasim Ali; Gamal Awad El-Shaboury; Haitham Ibrahim El-Mekkawy (Journal of Soil Science and Plant Nutrition, 2026)

Hyaluronic acid-functionalized liposomes as a nanoplatform for enhanced pharmacokinetics and therapeutic efficacy in arthritis - Zakir Ali; Muhammad Junaid; Sibgha Batool; Sidra Aslam; Tofeeq ur Rehman; Ali H. Alamri; Adel Al Fatease; Nabil K. Alruwaili; Majed A Alghamdi; Han-Gon Choi; Fakhar ud Din (Journal of Pharmaceutical Investigation, 2026)

Index based assessment of coastal vulnerability along the West Coast of Peninsular Malaysia: Evidence of climate change and anthropogenic impacts - Sreenivasulu Ganugapenta; Effi Helmy Ariffin; Wenjian Li; Siti Nur Hanani Zainuddin; Mohammad Ikhmal Siddiq Jefri Din; Masha Nur Salsabiela Menhat; Nurwani Mohd Zaki; Mardiha Mokhtar; Muhammad Rizal Razali; Khairul Nizam Abdul Maulud; Mohd Fuad Miskon (Ocean & Coastal Management, 2026)

Evaluating Lemna minor for bioethanol production and bioremediation of petrochemical wastewater - Fozia Shafiq; Ihsan ud din; Arif Ali Khattak; Muhammad Afzal (Biomass and Bioenergy, 2026)

A comprehensive review on thermo-responsive targeted and functional therapy for management of rheumatoid arthritis - Huma Hameed; Syed Sharf ud Din; Muhammad Zaman; Muhammad Ahsan Waqar; Kainat Fatima; Abdullah Ashraf; Huzaifa Malik; Ahmad Salawi (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Heavy metal contamination in agricultural soils: an environmental and food safety perspective - Siraj ud Din; Muhammad Subhanullah; Bakht Rawan; Shahla Nazneen; Muhammad Ilyas; Thiago Machado da Silva Acioly; Waheed Ullah; Abdullah Faiz Al Asmari; Saiful Islam (Environmental Monitoring and Assessment, 2026)

Eucalyptus wood waste biochar as an eco-friendly adsorbent for arsenic detoxification in wastewater - Yu Shuang Ren; Muhammad Ilyas; Islamud Din; Syeda Maria Ali; Shahid Iqbal; Thiago Machado da Silva Acioly; Zhanate Idrisheva; Khalid Z. Elwakeel; Alibek Ydyrys; Abdullah Faiz Al Asmari; Saiful Islam (Natural Product Research, 2026)

Insights into performance degradation of roof runoff treatment in field-scale bioretention facilities packed with zeolite and volcanic rock over three years of continuous operation - Jiakai Hu; Ronghua Xu; Jingyi Jiang; Muhammad Rizwan; Mohd Fadhil Md Din; Elsayed Ali Elsayed Ali; Eli Hendrik Sanjaya; AbdelGawad Saad; Zhe Kong; Hong Chen (Journal of Environmental Chemical Engineering, 2026)

Exploring the biocatalytic potential of Amycolatopsis japonica DyP in degrading plasticizer and phenolic-derived xenobiotic compounds - Muhammad Naveed; Ayesha Saleem; Tariq Aziz; Sadia Jabeen; Sana Miraj Khan; Maida Salah Ud Din; Nantenaina Tombozara; Mayasar I. Al-zaban; Ashwag Shami; Hayam A. Alwabsi (Biodegradation, 2026)

Molecular characterization and genetic diversity of cotton whitefly Bemisia tabaci infesting cotton crops - Qamar Saeed; Muhammad Sagheer; Ummad ud din Umar; Muhammad Taimoor Shakeel; Mahmoud Moustafa; Mohammed Al-Shahrani; Uthman Algopishi; Muhammad Naeem; Mahmoud Ahmed Amer (International Journal of Tropical Insect Science, 2026)

Integrating noninvasive genetics and SECR to estimate snow leopard population in Pakistan - Shakeel Ahmad; Katherine A. Solari; Ian Durbach; Hussain Ali; Shoaib Hameed; Jaffar Ud Din; Muhammad Asif; Dmitri A. Petrov; Muhammad Ali Nawaz (Biological Conservation, 2026)

Biosynthesis and Biological Assessment of TiO₂ Nanoparticles from Pittosporum Tobira for Antioxidant, Anti-Inflammatory, Anti-Hemolytic Potential, and Polychlorinated Biphenyls Degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Saman Nasir; Maida Salah Ud Din; Nawal Al-Hoshani; Maher S. Alwethaynani; Maymounah A. Alrayyani; Fakhria A. Al-Joufi (Water, Air, & Soil Pollution, 2026)

Integrating phenotypic, antioxidant, and molecular analyses to identify drought-tolerant wheat genotypes for climate resilience and genetic improvement - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Mueen Alam Khan; Muhammad Irfan Akram; Rashid Iqbal; Sajid Hussain; Muhammad Danial Shafiq; Mohamed El-Zaidy; Islem Abid (Cereal Research Communications, 2026)

Water Quality deterministic and Probabilistic Health Risks Assessment using Monte Carlo Simulation: Case Study from a Semi-Arid Region - Said Muhammad; Zeeshan Raza; Wajid Ali; Ashfaq Ahmad; Cem Tokatli; Imran Ud Din (Water, Air, & Soil Pollution, 2026)

Tissue-specific Ca2+ profiles associated with differential Ca2+ signalling and salinity stress tolerance between quinoa and spinach - Mohsin Tanveer; Waqas ud Din Khan; Muhammad Obeid Alshaharni; Caroline Ivsic; Zhong-Hua Chen; Lei Wang; Sergey Shabala (Plant and Soil, 2026)

Truncated Variants in FAM20A and WDR72 Genes Underlie Autosomal Recessive Amelogenesis Imperfecta in Four Pakistani Families - Sadaqat Ullah; Sher Alam Khan; Samin Jan; Salah Ud Din; Nazif Muhammad; Zia Ur Rehman; Abid Jan; Muhammad Tariq; Noor Muhammad; Abdul Ghani; Naveed Wasif; Saadullah Khan (Biochemical Genetics, 2026)
Amelogenesis Imperfecta (AI) is a set of hereditary diseases affecting enamel development, leading to various types of enamel defects, potentially impacting oral health unassociated with other generalized defects. AI manifests in syndromic and non-syndromic forms and can be inherited through autosomal recessive, autosomal dominant, or X-linked inheritance patterns. Genetic studies have identified sequence variants in a number of genes (≥ 70) linked to both syndromic and non-syndromic AI, highlighting the genetic diversity underlying the condition. The current study involved clinical evaluation and exome sequencing, aimed at identifying the causative variants in four unrelated consanguineous Pakistani families presenting AI phenotypes. The exome sequencing results revealed a novel homozygous frameshift variant FAM20A : NM_017565.4, c.188dupA; p.(Asp63Glufs*17) in families A, B, and C while a nonsense homozygous variant WDR72 : NM_182758.4, c.2686C > T; p. (Arg896*) in family D. The segregation of both variants was confirmed by Sanger sequencing. Bioinformatics analysis predicted the pathogenicity of these genetic variants. These alterations suggest functional consequences, potentially impairing the FAM20A and WDR72 proteins and causing dental anomalies. This investigation significantly broadens our understanding of FAM20A and WDR72 ’s involvement in AI. Furthermore, this study highlights the genetic heterogeneity of AI (involving FAM20A and WDR72 in this study) within the Pakistani population.

Molecular identification of the blaOXA gene in Bacillus cereus and AI-driven optimization of natural phytochemicals for foodborne illness treatment - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Maida Salah Ud Din; Muhammad Nouman Majeed; Ammena Y. Binsaleh; Nawal Al-Hoshani; Maher S. Alwethaynani; Abeer M. Alghamdi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2026)

Fate and transport of viruses in the subsurface environment: A systematic review of pollution pathways in saturated and unsaturated porous media - Muhammad Yousuf Jat Baloch; Purnima Baidya; Manita Aryal; Muhammad Moeen-ud-din; Liu Yang; Javed Iqbal; Mariusz Ptak; Predrag llić; Chunguang Liu (Environmental Research, 2026)

Anti-arthritic appraisal of Acorus calamus L. extracts in complete Freund’s adjuvant‑induced arthritic Wistar rats via regulating inflammatory cytokines and OPG/RANKL pathway - Muhammad Usman Bari; Asif Hussain; Bilal Aslam; Zia-ud-Din Sindhu; Muhammad Rehan Sajid; Rifat Ullah Khan (Inflammopharmacology, 2026)

Apple peel fermentation by Lactobacillus plantarum: Phytochemical transformations and enhanced abilities against inhibition of advanced glycation end products - Muhammad Nawaz; Hafiz Muhammad Rizwan; Zia Ud Din Momand; Irfan Ullah; Jiayi He; Qian Zhou; Mingfu Wang (Food Chemistry, 2025)

Recovery of Coral Reefs: Changes in Hard Coral Cover at Pulau Bidong After a Tropical Storm - Mohmad Fuad Nur Qamarina; Marsya Maisarah Ahmad Zaimi; Siti Nurtahirah Jaafar; Muhammad Hafiz Borkhanuddin; Zainudin Bachok; Che Din Mohd Safuan (Thalassas: An International Journal of Marine Sciences, 2025)

Beta-Glucan in barley as a natural immunomodulator: mechanisms and therapeutic potential - Hafiz Ghulam Muhu Din Ahmed; Li’E Yang; Xiaomeng Yang; Jiazhen Yang; Sajid Hussain; Muhammad Danial Shafiq; Muhammad Irfan Akram; Muhammad Sajad; Yawen Zeng (Molecular Biology Reports, 2025)

Spatial Distribution, Characterization and Ecological Risk Assessment of Microplastic Pollution in Different Environmental Matrices of River Ravi, Pakistan - Sara Shamshad; Safdar Sidra; Asia Iqbal; Aamna Ishaq; Afzal Nimra; Muhammad Muddassir Ali; Syed Ghulam Mohayud Din Hashmi; Muhammad Rashid; Fariha Arooj; Abdul Qadir; Rida Ahmad; Zulfiqar Ali (International Journal of Environmental Research, 2025)

Revolutionizing energy and logistics: a multilayered strategy for optimizing distribution networks and achieving dual carbon goals - Sajad Ali; Min Yongzhi; Chen Xin; Jalalud Din; Muhammad Salman (Clean Technologies and Environmental Policy, 2025)

Spatiotemporal heterogeneity of evapotranspiration controlling factors and their trends in Pakistan - Najeebullah Khan; Mohammed Magdy Hamed; Mohd Khairul Idlan Muhammad; Salah ud Din; Zulhilmi Ismail; Shamsuddin Shahid (Acta Geophysica, 2025)
Effective climate change mitigation planning in the water and agriculture sectors necessitates a thorough understanding of trends in potential evapotranspiration (ETp) and its driving factors. This study quantitatively assessed the impact of varying meteorological conditions on ETp across Pakistan. We deciphered the dynamics of recent ETp shifts by analyzing trends in meteorological variables using Princeton Global Meteorological Forcing data (daily maximum and minimum temperatures, wind speed, solar radiation, and relative humidity) at 0.25° resolution. Sobol's sensitivity analysis quantified the influence of each climatic variable on ETp. Nonparametric statistical tests identified trends in ETp and its influencing factors. Our findings reveal wind speed as the most critical element controlling ETp across all seasons in Pakistan, followed by solar radiation and temperature. Daily ETp exhibited increasing trends in the north, west, and east, ranging from 0.05 to 0.4 mm/decade. This rise in ETp can be primarily attributed to increasing temperatures, while other parameters like wind speed and solar radiation remained relatively constant. These results suggest that continued global warming-driven ETp increases may pose significant challenges for Pakistan's water supply and agricultural irrigation systems.

Water quality, risk assessment indices, and source apportionment across spatial patterns - Said Muhammad; Nizam Ullah; Wajid Ali; Sehrish Amin; Cem Tokatli; Imran Ud Din; Zafar Iqbal; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Simulation-based assessment of the impact of conservation tillage and strip intercropping on soil microbial biomass carbon - Sana ur Rehman; Xiaoping Xin; Shahzada Sohail Ijaz; Shroz Fatima; Ayesha Siddiqa; Hayder Bin Khalid; Imran Haider; Rashid Iqbal; Aqib Mahmood; Sajad Hussain; Atta Mohi Ud Din; Taqi Raza; et al. (CATENA, 2025)

Retraction Note: Integrated agri-aquaculture of Lactuca sativa and Cyprinus carpio improve yield and economic benefits of small-scale farmers - Sanaullah Sattar; Muhammad Muneeb; Abdul Majeed Saim; Wali Muhammad Mangrio; Farhan Nabi; Muhammad Bilawal Junaid; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Imran Haider; Rashid Iqbal (Aquaculture International, 2025)

Artificial neural network optimized green synthesis of cysteine-conjugated silver nanoparticles for antibacterial activity against staphylococcus nepalensis to combat cystitis - Muhammad Asim; Muhammad Naveed; Tariq Aziz; Maida Salah Ud Din; Fatma Alshehri; Ashwag Shami; Maher S. Alwethaynani; Deema Fallatah; Abeer M. Alghamdi; Fakhria A. Al-Joufi (Antonie van Leeuwenhoek, 2025)

Kaempferol alleviates cypermethrin induced reproductive toxicity in rats via Nrf2-mediated antioxidant and apoptotic regulation with histopathological evidence: in vivo and in silico study - Fahad Kabeer; Shaista Anjum; Atique Ahmed Behan; Muhammad Usman; Nazima Yousaf khan; Muhammad Azeem; Hafiz Misbah Ud Din; Muhammad Adeel Arshad; Sadaf Nazir; Shiping Cheng; Jameel Ahmed Buzdar (Journal of Molecular Histology, 2025)

Image segmentation and machine learning modelling for water status determination and precision irrigation management - Hamza Salah Ud Din; Aqib Iqbal; Fazal Jalal; Awais Ahmad; Muhammad Haris Paracha; Shah Fahad; Zafar Hayat Khan; Shah Saud; Taufiq Nawaz (Journal of Crop Science and Biotechnology, 2025)

Molecular characterization and green synthesis of iron oxide nanoparticles from Ureibacillus chungkukjangi for methylene blue degradation - Muhammad Naveed; Muhammad Asim; Tariq Aziz; Shumaila Ibrahim; Maida Salah Ud Din; Maryam M. Alomran; Ashwag Shami; Fakhria A. Al-Joufi; Ahmad A. Alghamdi; Abdullah A. Alqasem; Ahmed M. Basri; Majid Alhomrani (Antonie van Leeuwenhoek, 2025)

Spatial distribution, potential health risks, and sources of groundwater contamination in the semi-arid region - Owais Rabbani; Wajid Ali; Ghazanfar A. Khattak; Said Muhammad; Muhammad Nafees; Shahid Iqbal; Imran Ud Din; Ashfaq Ahmad; Umar Farooq (Physics and Chemistry of the Earth, Parts A/B/C, 2025)

Plant-derived green metal nanoparticles as antibacterial, antifungal, and therapeutic agents: Advances, challenges, and perspectives - Rabia Zafar; Azeem Intisar; Muhammad Imran Din; Ahsan Sharif; Ejaz Ahmed; Adeel Afzal (Bioresource Technology Reports, 2025)

Comparative assessment of biochar and vermicompost on chromium bioavailability and stress alleviation in tomato (Solanum lycopersicum) - Jamaluddin Kabir; Muhammad Ansar Farooq; Shumaila Parvez; Aamir Alaud Din; Ghulam Abbas; Minggang Xu; Muhammad Mohsin Abrar (Journal of Soils and Sediments, 2025)

Maize/Legume Intercropping Increases Nutrient Uptake, Crop Yields, Land Productivity, and Economic Profits in Resource-intensive Arid-irrigated Areas - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Ghulam Abbas Shah; Wang Zhiqi; Muhammad Jawad Hassan; Muhammad Bilal; Harun Gitari; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Unleashing the Prospects of Value-Added Soil Amendments for Remediation of Salt-Affected Soils and Carbon Storage - Zia Ur Rahman Farooqi; Ayesha Abdul Qadir; Anam Naz; Waqas Mohy-Ud-Din; Elaheh Daghighi; Muhammad Tauseef Jaffar; Muhammad Ahmed; Hayssam M. Ali; Waleed A. A. Alsakkaf (Journal of Soil Science and Plant Nutrition, 2025)

Identification of a Novel GRM1 Frameshift Variant in Two Pakistani Families Broadens the Genetic Landscape of Ultra-Rare Spinocerebellar Ataxia Type 13 - Riaz Ahmad; Mina Zamani; Eleanor Self; Salah Ud Din Shah; Muhammad Naeem; Henry Houlden (The Cerebellum, 2025)
Autosomal recessive spinocerebellar ataxia 13 (SCAR13) is an extremely rare neurodegenerative disorder characterized by psychomotor delay, ranging from mild to severe intellectual disability with absent or poor speech development, nystagmus and stance ataxia. If ambulation is achieved, affected subjects often exhibit gait ataxia. Additionally, epilepsy and polyneuropathy have been reported in some patients. SCAR13 is caused by pathogenic variants in the GRM1 gene, which is predominantly expressed in the cerebellum, with lower levels in the other parts of the brain. To date, only seven reports of this rare ataxia have been published globally. Our study aimed to investigate clinical and mutation spectrum of GRM1 -associated SCAR13 disorder in nine patients of two consanguineous Pakistani families (designated here to as NP35 and NP36). We performed whole exome sequencing in the probands of the two families followed by Sanger sequencing to test variant segregation. We identified a novel GRM1 frameshift variant (NM_001278064.2):c.3525_3529del; p.(Asn1176IlefsTer71) in both families as a cause of SCAR13. It was classified as a variant of uncertain significance (PM2: pathogenic moderate 2 and PVS1: pathogenic very strong 1) according to the ACMG guidelines. The novel variant exhibited clinical heterogeneity in the two families. Moreover, scoliosis was observed in all four patients of the family NP35, a feature previously documented in only one patient worldwide. Our study expands the limited mutation spectrum of the GRM1 -associated SCAR13. Next-generation sequencing plays a pivotal role in the elucidation of inherited neurological disorders and in a better understanding of the convergent phenotypes.

Utilizing genetic resources to develop yellow rust-resistant and high-yielding wheat genotypes across diverse environments - Hassan Mujtaba; Fahim Ullah Khan; Muhammad Sufyan; Israr Ud Din; Manzoor Ahmad; Asad Shah; Umair Bin Qasim (Genetic Resources and Crop Evolution, 2025)

High-Sensitivity RT-LAMP Assay Enables Rapid, Field-Deployable Detection of Candidatus Liberibacter Asiaticus in Crude DNA Extracts from Citrus Phyllosphere and Psyllid Vectors - Ummad ud Din Umar; Syed Muhammad Zaka; Muhammad Nauman Tahir; Muhammad Kashif; Ateeq Ur Rehman; Sagheer Atta; Syed Atif Hasan Naqvi (Applied Fruit Science, 2025)

Mango Tree Sudden Decline disease: 65-years global perspective of ecology, biology, epidemiology, and management - Challenge of tropical landscape pathology - Syed Atif Hasan Naqvi; Muhammad Tariq Malik; Ummad Ud Din Umar; Ateeq Ur Rehman; Shakeel Ahmad; Muhammad Fahad Hakim; Ghulam Mustafa; Muhammad Farhan; Rogério Machado Pereira; Tarcísio Visintin da Silva Galdino; Marcelo Coutinho Picanço; Ricardo Siqueira da Silva (Physiological and Molecular Plant Pathology, 2025)

7β-(3-ethyl-cis-crotonoyloxy)-1α-(2-methylbutyryloxy)-3,14-dehydro-Z-notonipetranone (ECN) attenuates inflammation and oxidative stress via MAPK, and Nrf2/HO-1 signaling in Traumatic brain injury - Sana Zafar; Maryam Jamil; Muhammad Ibrar Khan; Fakhar ud Din; Eun Kyoung Seo; Salman Khan (Chemico-Biological Interactions, 2025)

Evaluating the efficacy of nano-cyclosporine A in mice model of ulcerative colitis: a meta-analysis - Aqsa Mehreen; Faiza Batool; Uzma Azeem Awan; Nadia Shabnam; Adnan Haider; Shaista Aslam; Madiha Ghazanfar; Fakhar Ud-Din; Muhammad Irfan Siddique; Muhammad Naeem; Rida Fatima Saeed (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Advanced characterization of hemp biomass pyrolysis: Bioenergy recovery and environmental implications - Rashid Minhas; Asif Hussain Khoja; Hajirah Kanwal; Muhammad Hassan; Arslan Khan; Syed Sheraz Daood; Israf Ud din; Ali Bahadar (Sustainable Chemistry and Pharmacy, 2025)

Correction: Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Combined Effects of Reduced Tillage and Strip Intercropping on Soil Carbon Sequestration in Semi-Arid Environment - Sana ur Rehman; Shahzada Sohail Ijaz; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Muhammad Ansar; Shroz Fatima; Ayesha Siddiqa; Muhammad Nadeem Ashraf; Imran Haider; Muhammad Bilawal Junaid; Muhammad Ali Raza; Haishui Yang (Journal of Soil Science and Plant Nutrition, 2025)

Biochar and Pseudomonas aeruginosa M2 Co-Application: A Sustainable Strategy for Enhancing Growth and Heavy Metal Tolerance in Brassica campestris - Muhammad Muzammil Mukhtar; Qasim Ali; Muhaimen Ayyub; Muhammad Aon; Hayssam M. Ali; Sadaf Oranab; Iftikhar Ahmad; Ghulam Abbas; Behzad Murtaza; Waqas Mohy-Ud-Din; Usman Zulfiqar; Muhammad Faisal Maqsood; et al. (Journal of Soil Science and Plant Nutrition, 2025)

Genetic diversity in wheat landraces for agronomic traits and yellow rust resistance - Shamim Khan; Niaz Ali; Fahim Ullah Khan; Israr Ud Din; Muhammad Amjad; Israr Ahmad (Genetic Resources and Crop Evolution, 2025)

Molecular marker based analysis of allelic variation in the spring wheat genome - Hafiz Ghulam Muhu Din Ahmed; Tao Yang; Muhammad Irfan Akram; Rashid Iqbal; Abdullah Ahmed Al-Ghamdi; Dunia A. Al Farraj (Genetic Resources and Crop Evolution, 2025)

Bioactive Metabolites from Radioresistant Bacterium Kocuria sp. TMM 11 and Their Role in Prevention of Ultraviolet-Induced Photodamages - Tayyaba Alam; Salah Ud Din; Muhammad Abdullah; Mahwish Ali; Malik Badshah; Muhammad Farman; Samiullah Khan; Fariha Hasan; Aamer Ali Shah (Current Microbiology, 2025)

Metal sulfides in aged-coarse sands tailings facilitate naphthenic acids removal from oil sands process water - Muhammad Arslan; Muhammad Usman; Mohamed Gamal El-Din (Water Research, 2025)

Quantitative analysis of pathogenesis-related protein expression in Gossypium hirsutum L. to elicitor-induced resistance against cotton leaf curl disease and predicted in-silico protein-protein interactions - Muhammad Fahad Khan; Syed Atif Hasan Naqvi; Adnan Iqbal; Seth Alan Steichen; Amjad Ali; Rana Muhammad Amir Gulzar; Judith K. Brown; Ummad Ud Din Umar (Physiological and Molecular Plant Pathology, 2025)

PFAS insights: A review of historical data, environmental applications, health effects, and pollution challenges in Pakistan - Amna Chaudhary; Waqas Bashir; Abdul Majid; Muhammad Qasim; Erum Bughio; Minahal Fatima; Siraj U Din (Environmental Science & Policy, 2025)

Extreme thermophilic microbial inoculation for reducing NH3 and N2O emissions in hyperthermophilic aerobic composting of refinery waste activated sludge - Xinge Fu; Hui Zuo; Zhouhao Wang; Pengyin Shang; Zhuoyu Li; Jin Li; Yali Zhan; Qinghong Wang; Muhammad Arslan; Mohamed Gamal El-Din; Chunmao Chen (Journal of Environmental Management, 2025)

Yield gains and resource use advantages driven by legume choice and row ratio in cotton/legume intercropping under arid-irrigated conditions - Muhammad Ali Raza; Atta Mohi Ud Din; Hassan Shehryar Yasin; Hina Gul; Amjad Saeed; Aqib Mehmood; Sana Ur Rehman; Zafar Iqbal; Rashid Iqbal; Noorah Al Kubaisi; Mohamed S. Elshikh; Ghulam Abbas Shah; et al. (Field Crops Research, 2025)

Estimation and geographical mapping of enteric methane emission from large ruminants under different production systems in Pakistan - Nasir Ali; Muhammad Qamar Shahid; Nisar Ahmad; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2025)

Correction to: Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-Ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Role of the plant nurseries in spread of invasive alien plant species in Pakistan’s subtropical region; A threat for urban greening - Maria Shah; Shujaul Mulk Khan; Fazal Manan; Jawad Hussain; Zohaib U. Din; Imranullah Shah; Muhammad Arshad; Israr Ahmad (Urban Forestry & Urban Greening, 2025)

Manipulation of root-associated bacterial endophytes for sustainable crop production system: A review - Maqsood Ahmed Khaskheli; Mir Muhammad Nizamani; Entaj Tarafder; Diptosh Das; Ghulam Muhae-Ud-Din; Raheel Ahmed Khaskheli; Yong Wang (Rhizosphere, 2025)

Impact of Storm Pabuk on a Monsoon Coral Beach: Bidong Island, Terengganu (Malaysia) - Siti Nur Hanani Zainuddin; Che Din Mohd Safuan; Junainah Zakaria; Cherdvong Saengsupavanich; Muhammad Zahir Ramli; Azizi Ali; Zainudin Bachok; Fatihah Shariful; Alya Syakirah Tajul Ariffin; Idham Khalil; Aidy M. Muslim; Hasrizal Shaari; et al. (Marine Geology, 2025)

Genomic selection, gene editing, and reproductive biotechnology: a triad for the improvement of native buffalo breeds in a developing country perspective like Pakistan - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ali Haider Saleem; Qudrat Ullah; Ghulam Abbas; Babar Maqbool; Masroor Ellahi Babar; Yanzhen Bi; Farhan Farooq (Tropical Animal Health and Production, 2025)

Asymmetric role of board diversity on green growth mechanism: Evidence from COP27 framework - Kamran Mohy-ud-Din; Muhammad Shahbaz; Shoh-Jakhon Khamdamov; Shabbir Ahmad (Journal of Environmental Management, 2025)

Corrigendum to ‘Trace element bioaccumulation in edible red seaweeds (Rhodophyta): A risk assessment for consumers’ [Environ. Pollut. 307 (2022) 1–10/119560] - Md Solaiman Hossain; Eurida Liyana; Saad Al-din Sifat; Fuad Ameen; Md Akram Ullah; Yeasmin Nahar Jolly; Shamshad Begum Quraishi; Mofazzal Hossain; Sazlina Salleh; Sharmin Akter; Mohammad Afzal Hossain; Muhammad Zobayer Bin Mukhlish; et al. (Environmental Pollution, 2025)

RETRACTED ARTICLE: Integrated agri-aquaculture of Lactuca sativa and Cyprinus carpio improve yield and economic benefits of small-scale farmers - Sanaullah Sattar; Muhammad Muneeb; Abdul Majeed Saim; Wali Muhammad Mangrio; Farhan Nabi; Muhammad Bilawal Junaid; Atta Mohi Ud Din; Munirah Abdullah Al-Dosary; Imran Haider; Rashid Iqbal (Aquaculture International, 2025)

Use of methanolic plant extracts against maize weevil (Sitophilus zeamais) (Curculionidae: Coleoptera) - Muhammad Mamoon-ur-Rashid; Riaz-ud Din; Muhammad Naeem; Mohamed Farouk Elsadek; Khalid S. Al-Numair; Mohamed S. Sheteiwy; Iram Ijaz; Muhammad Muzammal; Muhammad Yasin (International Journal of Tropical Insect Science, 2025)

Sustainable bioenergy potential of peat-moss derived hydrothermal aqueous phase: Insights into methane production and organic transformation - Muhammad Usman; Gang Luo; Mohamed Gamal El-Din (Bioresource Technology, 2025)

Thermokinetic investigation of Polyethylene Terephthalate (PET) plastic over biomass fly ash (BFA) catalyst using pyrolysis process through non-isothermal thermogravimetric analysis - Ali Raza; Waqar Ul Habib Khan; Asif Hussain Khoja; Arslan Khan; Muhammad Hassan; Rabia Liaquat; Majid Ali; Israf Ud Din; Abdulaziz Al-Anazi (Sustainable Chemistry and Pharmacy, 2024)

Potentially harmful elements contamination, risk assessment, and their bioaccumulation in food crops - Imran Ud Din; Said Muhammad; Cem Tokatli; Inayat ur Rehman; Wajid Ali; Mohammed Rafi Shaik; Mohamed E. Assal; Ayaz Ul Haq; Shaik Althaf Hussain (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Survival strategies and assembly mechanisms of microbial communities in petroleum-contaminated soils - Wenyi Lu; Yi Zheng; Yi Wang; Jiayu Song; Yibin Weng; Wenfeng Ma; Muhammad Arslan; Mohamed Gamal El-Din; Dingyuan Wang; Qinghong Wang; Chunmao Chen (Environmental Research, 2024)

Sea level rise estimation and projection from long-term multi-mission satellite altimetry and tidal data in the Southeast Asia region - Muhammad Luqman Ahmad Affandi; Ami Hassan Md Din; Abd Wahid Rasib (International Journal of Remote Sensing, 2024)

The optimization of marine geoid model from altimetry data using Least Squares Stokes modification approach with additive corrections across Malaysia - Nornajihah Mohammad Yazid; Ami Hassan Md Din; Muhammad Faiz Pa’suya; Abdullah Hisam Omar; Nazirah Mohamad Abdullah; Mohammad Hanif Hamden (International Journal of Remote Sensing, 2024)

Earthworms as Catalysts for Climate-Resilient Agriculture: Enhancing Food Security and Water Management in the Face of Climate Change - Muhammad Danish Toor; Abdul Basit; Benedict Okorie; Dibyajyoti Nath; Muhammad Mughees Ud Din; Pawan Kumar Verma; Saleem Sajjad; Izhar Ullah; Hany N. Yousef; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

Integration of Local Mean Sea Level and Land Vertical Datum over Peninsular Malaysia via Transformation Model - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Noorfatekah Talib; Mohamad Azril Che Aziz; Muhammad Zahir Ramli; Mohammad Hanif Hamden; Nornajihah Mohammad Yazid (Pure and Applied Geophysics, 2024)

Artificial Intelligence-Based Classification of CT Images Using a Hybrid SpinalZFNet - Faiqa Maqsood; Wang Zhenfei; Muhammad Mumtaz Ali; Baozhi Qiu; Naveed Ur Rehman; Fahad Sabah; Tahir Mahmood; Irfanud Din; Raheem Sarwar (Interdisciplinary Sciences: Computational Life Sciences, 2024)
The kidney is an abdominal organ in the human body that supports filtering excess water and waste from the blood. Kidney diseases generally occur due to changes in certain supplements, medical conditions, obesity, and diet, which causes kidney function and ultimately leads to complications such as chronic kidney disease, kidney failure, and other renal disorders. Combining patient metadata with computed tomography (CT) images is essential to accurately and timely diagnosing such complications. Deep Neural Networks (DNNs) have transformed medical fields by providing high accuracy in complex tasks. However, the high computational cost of these models is a significant challenge, particularly in real-time applications. This paper proposed SpinalZFNet, a hybrid deep learning approach that integrates the architectural strengths of Spinal Network (SpinalNet) with the feature extraction capabilities of Zeiler and Fergus Network (ZFNet) to classify kidney disease accurately using CT images. This unique combination enhanced feature analysis, significantly improving classification accuracy while reducing the computational overhead. At first, the acquired CT images are pre-processed using a median filter, and the pre-processed image is segmented using Efficient Neural Network (ENet). Later, the images are augmented, and different features are extracted from the augmented CT images. The extracted features finally classify the kidney disease into normal, tumor, cyst, and stone using the proposed SpinalZFNet model. The SpinalZFNet outperformed other models, with 99.9% sensitivity, 99.5% specificity, precision 99.6%, 99.8% accuracy, and 99.7% F1-Score in classifying kidney disease. Graphical Abstract

Uncovering foraminiferal assemblages in Pulau Redang and the importance of FoRAM index calibration for reef monitoring in South China sea - Fatin Izzati Minhat; Che Din Mohd Safuan; Sabrina Alia Mohd Emran; Aida Farisah Mohd Hasnizul; Aminudin Muhammad Afiq-Firdaus; Zainudin Bachok; Wan Izatul Asma Wan Talaat (Marine Environmental Research, 2024)

Performance evaluation and microbial community succession analysis of co-composting treatment of refinery waste activated sludge - Xinge Fu; Hui Zuo; Yibin Weng; Zhouhao Wang; Yue Kou; Dingyuan Wang; Zhuoyu Li; Qinghong Wang; Muhammad Arslan; Mohamed Gamal El-Din; Chunmao Chen (Journal of Environmental Management, 2024)

RNA interference: a promising biotechnological approach to combat plant pathogens, mechanism and future prospects - Amjad Ali; Muhammad Shahbaz; Fatih Ölmez; Noor Fatima; Ummad Ud Din Umar; Md. Arshad Ali; Muhammad Akram; Jaya Seelan Sathiya Seelan; Faheem Shehzad Baloch (World Journal of Microbiology and Biotechnology, 2024)

Microbial Ecosystems as Guardians of Food Security and Water Resources in the Era of Climate Change - Muhammad Danish Toor; Muneeb Ur Rehman; Javeria Abid; Dibyajyoti Nath; Izhar Ullah; Abdul Basit; Muhammad Mughees Ud Din; Heba I. Mohamed (Water, Air, & Soil Pollution, 2024)

Evaluation of carob tree (Ceratonia siliqua L.) pods, through three different drying techniques, and ultrasonic assisted extraction, for presence of bioactives - Ashiq Hussain; Muhammad Rehan Arif; Adnan Ahmed; Salah Laaraj; Nida Firdous; Muhammad Qasim Ali; Haya Fatima; Shazia Yaqub; Samina Kauser; Rizwan Nisar; Faiza Iftikhar Gorsi; Ghulam Mueen Ud Din; et al. (South African Journal of Botany, 2024)

Distribution, diel activity patterns and human-bear interactions of the Himalayan brown bear (Ursus arctos isabellinus) in the Deosai National Park, Pakistan - Tosif Fida; Faizan Ahmad; Luciano Bosso; Neeha Ali; Shams Ud Din; Muhammad Kabir (Mammal Research, 2024)

Genetic Association Among Morpho-Physiological Attributes Against Heat Tolerance in Rice Genotypes - Hafiz Ghulam Muhu-Din Ahmed; Noor Fatima; Yawen Zeng; Muddassir Hussain; Muhammad Moaaz Mushtaq; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Adnan Noor Shah; Hayssam M. Ali; Mohamed M. A. Abdelhamid; Sezai Ercisli (Journal of Crop Health, 2024)

Legume choice and planting configuration influence intercrop nutrient and yield gains through complementarity and selection effects in legume-based wheat intercropping systems - Muhammad Ali Raza; Atta Mohi Ud Din; Ghulam Abbas Shah; Wang Zhiqi; Ling Yang Feng; Hina Gul; Hassan Shehryar Yasin; Mohammad Shafiq ur Rahman; Chen Juan; Xue Liang; Raheela Rehman; Amal Mohamed Al Garawi; et al. (Agricultural Systems, 2024)

A holistic overview of the in-situ and ex-situ carbon mineralization: Methods, mechanisms, and technical challenges - Farzain Ud Din Kirmani; Arshad Raza; Sheraz Ahmad; Muhammad Arif; Mohamed Mahmoud (Science of The Total Environment, 2024)

Impact of truncated modified basalt fibers on aerobic granular sludge stability and pollutant removal in piggery wastewater treatment - Yun Zhou; Xiaochun Wang; Muhammad Arslan; Xiangtong Zhou; Zhiren Wu; Jianxun Liu; Xueyan Li; Mohamed Gamal El-Din (Chemical Engineering Journal, 2024)

Foliar Application of Moringa and Mint Leaf Extracts Enhances Carnation Growth and Flower Yield Under Saline Conditions by Improving Plant Defense Mechanism - Hafiza Muniba Din Muhammad; Muhammad Akbar Anjum; Riaz Ahmad; Sezai Ercisli (Journal of Plant Growth Regulation, 2024)

Quantification and polymeric characterization of microplastics in composts and their accumulation in lettuce - Aamna Naeem; Muhammad Ansar Farooq; Muhammad Shafiq; Muhammad Arshad; Aamir Alaud Din; Abdulrahman Ali Alazba (Chemosphere, 2024)

Desorption and migration of dissolved organics from oil sands tailings to capped water: Demonstration pit lake - Foroogh Mehravaran; Muhammad Arslan; Xiaoying Fan; Mohamed Gamal El-Din (Chemical Engineering Journal, 2024)

Optimizing Micronutrient Supplementation in Mango Orchards for the Suppression of Mango Anthracnose (Colletotrichum gloeosporioides) - Wajid Nazir; Syed Atif Hasan Naqvi; Niaz Ahmed; Ateeq ur Rehman; Abdulwahed Fahad Alrefaei; Muhammad Asif Zulfiqar; Ummad ud Din Umar (Applied Fruit Science, 2024)

Glycolipids biosurfactants production using low-cost substrates for environmental remediation: progress, challenges, and future prospects - Muhammad Aqif; Mansoor Ul Hassan Shah; Rawaiz Khan; Muhammad Umar; SajjadHaider; Saiful Izwan Abd Razak; Mat Uzir Wahit; Salah Ud-Din Khan; Magaret Sivapragasam; Shafi Ullah; Rab Nawaz (Environmental Science and Pollution Research, 2024)

Molecular and microbial insights towards anaerobic biodegradation of anionic polyacrylamide in oil sands tailings - Jia Li; Muhammad Usman; Muhammad Arslan; Mohamed Gamal El-Din (Water Research, 2024)

Estimation of the zero-height geopotential value and datum offset for the Kenya vertical network using an optimized earth model - Chivatsi Jonathan Nyoka; Ami Hassan Md Din; Muhammad Faiz Pa'suya (Journal of African Earth Sciences, 2024)

Corrigendum to “Current challenges of hydrothermal treated wastewater (HTWW) for environmental applications and their perspectives: A review” [Environ. Res. 212 Part D (2022) 113532] - Muhammad Usman; Zhijian Shi; Nalok Dutta; Muhammad Awais Ashraf; Bushra Ishfaq; Mohamed Gamal El-Din (Environmental Research, 2024)

Sugarcane/soybean intercropping enhances crop productivity, nutrient uptake, and net economic return with reduced inputs - Muhammad Ali Raza; Atta Mohi Ud Din; Hina Gul; Wang Zhiqi; Hassan Shehryar Yasin; Muhammad Hayder Bin Khalid; Nasir Iqbal; Amjad Saeed; Birra Bukhari; Munirah Abdullah Al Dosary; Chen Juan; Xue Liang; et al. (Field Crops Research, 2024)

The potential effects of N-Acyl homoserine lactones on aerobic sludge granulation during phenolic wastewater treatment - Shasha Liu; Qinghong Wang; Jiahao Liang; Jin Li; Zhiguo Shao; Yehua Han; Muhammad Arslan; Mohamed Gamal El-Din; Zhuoyu Li; Chunmao Chen (Environmental Research, 2024)

Salicylic Acid-Induced Antioxidant Defense System Alleviates Cadmium Toxicity in Wheat - Umer Hayat; Kaleem ul din; Arslan Haider; Tahrim Ramzan; Bilal Ahmad Shahzad; Muhammad Ahmad; Usman Zulfiqar; Muhammad Faisal Maqsood; Sadam Hussain; Mona S. Alwahibi; Mohamed S. Elshikh (Journal of Soil Science and Plant Nutrition, 2024)

Silicon-Mediated Alleviation of Salinity Stress in Petunia (Petunia hybrida) by Modulation of Morphological, Physiological and Biochemical Indices - Hafiza Muniba Din Muhammad; Muhammad Akbar Anjum; Safina Naz (Journal of Soil Science and Plant Nutrition, 2024)

Exploring nature's filters: Peat-mineral mix for low and high-strength oilfield produced water reclamation - Muhammad Arslan; Muhammad Usman; Mohamed Gamal El-Din (Water Research, 2024)

Trapping the genetic variation for yield and yield related attributes in bread wheat under water deficit stress - Hafiz Ghulam Muhu-Din Ahmed; Muhammad Naeem; Yawen Zeng; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Irfan Akram; Amjad Saeed; Noor Fatima; Ibtasam Moeez; Hayssam M. Ali; Nagy S. Radwan; Sezai Ercisli; et al. (Euphytica, 2024)

Divergent responses of phosphorus solubilizing bacteria with P-laden biochar for enhancing nutrient recovery, growth, and yield of canola (Brassica napus L.) - Muhammad Farhan Qadir; Muhammad Naveed; Khuram Shehzad Khan; Tooba Mumtaz; Taqi Raza; Waqas Mohy-Ud-Din; Adnan Mustafa (Chemosphere, 2024)

From stress to success: Silicon and nano-silicon strategies for enhancing fruit yield and quality in cadmium-exposed trees - Riaz Ahmad; Hafiza Muniba Din Muhammad; Safina Naz; Rahul Kumar Tiwari; Milan Kumar Lal; Parvaiz Ahmad; Muhammad Ahsan Altaf (South African Journal of Botany, 2024)

Spatial distribution and potential health risk assessment for fluoride and nitrate via water consumption in Pakistan - Imran Ud Din; Wajid Ali; Said Muhammad; Mohammed Rafi Shaik; Baji Shaik; Inayat ur Rehman; Cem Tokatli (Journal of Geochemical Exploration, 2024)

Remediation of phenanthrene-contaminated soil by iron oxide/carboxylate-rich porous carbon composites from vinegar residue - Zhijun Luo; Huan Luo; Lingling Qu; Pamela Chelme-Ayala; Muhammad Arslan; Mohamed Gamal El-Din (Journal of Environmental Chemical Engineering, 2024)

Chlorangium ahmadii sp. nov. and Circinaria darelensis sp. nov. two new species of lichenized Ascomycetes from Pakistan - Alla Ud Din; Muhammad Shahid Iqbal; Abdul Nasir Khalid; Abdul Rehman Niazi (Plant Systematics and Evolution, 2024)

Heritability and Genotypic Association Among Seedling Attribute Against Salinity Stress Tolerance in Wheat Genotypes for Sustainable Food Security - Hafiz Ghulam Muhu-Din Ahmed; Yawen Zeng; Xiaomeng Yang; Anns Faisal; Noor Fatima; Aziz Ullah; Ghulam Sabir Hussain; Muhammad Iftikhar; Muhammad Rizwan Anwar (Journal of Crop Health, 2024)

Serum and salivary Cu/Zn ratio as a diagnostic biomarker for oral submucosal fibrosis: an analysis of trace metals and LOX gene variants - Rafia Shah; Feriha Fatima Khidri; Yar Muhammad Waryah; Roohi Nigar; Amber Mahmood; Hina Shaikh; Muhammad Qasim Awan; Ikram Din Ujjan; Ali Muhammad Waryah (BioMetals, 2024)

Optimization and cost analysis evaluation studies of the biodiesel production from waste cooking oil using Na–Si/Ce-500 heterogeneous catalyst - Mshari A Alotaibi; Abdul Naeem; Ihtisham Wali Khan; Muhammad Farooq; Israf Ud Din; Maizat S. Saharun (Biomass and Bioenergy, 2024)

Silicon-nanoparticles loaded biochar for soil arsenic immobilization and alleviation of phytotoxicity in barley: Implications for human health risk - Muhammad Asif Naeem; Abrar Shabbir; Muhammad Imran; Sajjad Ahmad; Muhammad Shahid; Behzad Murtaza; Muhammad Amjad; Waqas-ud-Din Khan (Environmental Science and Pollution Research, 2024)

Adopting Marine Spatial Planning (MSP) using coral health assessment as indicator: A case study in Pulau Redang Marine Park, Malaysia - Farhana Razak; Wei Yien Lua; Nor Hafzan Abd Rasid; Nazli Aziz; Izarenah Md Repin; Xiong-Zhi Xue; Abdul Rahman Muhammad Ashraf; Zainudin Bachok; Aminudin Afiq-Firdaus; Wan Izatul Asma Wan Talaat; Abdul Rahman Abdul Latip; Che Din Mohd Safuan (Ocean & Coastal Management, 2024)

How do digital inclusion and energy security risks affect mineral resources trade? Evidence from world-leading mineral trading countries - Muhammad Tayyab Sohail; Norashidah Md Din (Resources Policy, 2024)

Determination of Salinity Tolerance in Pigmented Rice Genotypes at Seedling Stage - Zeeshan Ali; Muhammad Naeem; Hafiz Ghulam Muhu-Din Ahmed (Journal of Crop Health, 2024)

Potential of two entomopathogenic fungi, Beauveria bassiana and metarhizium anisopliae as biocontrol agents of Rhpalosiphum padi and Shizaphis graminum, (Homoptera: Aphididae) in laboratory and field - Misbah Ashraf; Dilbar Hussain; Shahbaz Hussain; Naima Din; Qurban Ali; Muhammad Shah Jahan; Muhammad Yasin; Muhammad Farooq (International Journal of Tropical Insect Science, 2024)

The fourth industrial revolution in the food industry—part II: Emerging food trends - Abdo Hassoun; Alaa El-Din Bekhit; Anet Režek Jambrak; Joe M. Regenstein; Farid Chemat; James D. Morton; María Gudjónsdóttir; María Carpena; Miguel A. Prieto; Paula Varela; Rai Naveed Arshad; Rana Muhammad Aadil; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Role of the government towards stock markets and carbon emissions: evidence from wavelet approach - Muhammad Waris; Badariah Haji Din (Environmental Science and Pollution Research, 2024)

Exploration of microplastic concentration in indoor and outdoor air samples: Morphological, polymeric, and elemental analysis - Khadija Sharaf Din; Muhammad Fahim Khokhar; Shahid Ikramullah Butt; Abdul Qadir; Farhan Younas (Science of The Total Environment, 2024)

CRISPR/Cas9-based genome editing: A revolutionary approach for crop improvement and global food security - Ghulam Muha-Ud-Din; Faizan Ali; Akhtar Hameed; Syed Atif Hasan Naqvi; Mir Muhammad Nizamani; Muhammad Jabran; Sohaib Sarfraz; Wang Yong (Physiological and Molecular Plant Pathology, 2024)

Heavy metal(loid)s contamination and ecotoxicological hazards in coal, dust, and soil adjacent to coal mining operations, Northwest Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Journal of Geochemical Exploration, 2024)

How does formal credit promote green entrepreneurship? New insights from renewable energy producers in high-, middle-, and low-income countries - Muhammad Tayyab Sohail; Norashidah Md Din (Environmental Science and Pollution Research, 2023)

Nexus of the CSR disclosures and corporate financial performance: evidence from Asian countries climate policy uncertainty - Muhammad Waris; Badariah Haji Din (Environmental Science and Pollution Research, 2023)

Oxidative stress responses of the scleractinian coral Acropora digitifera from the tropical Bidong Island, Malaysia - focus on protein thiol groups' detection - Muhammad Arif Samshuri; Che Din Mohd Safuan; Siti Nurtahirah Jaafar; Chui Pin Leaw; Li Keat Lee; Mathinee Yucharoen; Zainudin Bachok (Journal of Experimental Marine Biology and Ecology, 2023)

Effects of prenatal dichromatic light exposure on hatching results and post-hatch performance of Japanese quail - Muhammad Safwan; Shahid Mehmood; Shahid Sherzada; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Shaheryar Ali; Abd ur Rehman; Muhammad Faisal Riaz; Usman Elahi; Murrawat Hussain; Hafiz Rao Abdul Latif; Kinza Saleem; et al. (Tropical Animal Health and Production, 2023)

Seaweed Application Enhanced the Growth and Yield of Pea (Pisum sativum L.) by Altering Physiological Indices - Safina Naz; Hafiza Muniba Din Muhammad; Muhammad Ramzan; Bushra Sadiq; Riaz Ahmad; Saqib Ali; Abdulaziz Abdullah Alsahli; Muhammad Ahsan Altaf (Journal of Soil Science and Plant Nutrition, 2023)

Annual effective dose estimation of radon in drinking water sources of Nizampur basin, North Western Pakistan - Jehangir Ijaz; Wajid Ali; Said Muhammad; Hayat Ullah; Danish Ather; Imran Ud Din (Isotopes in Environmental and Health Studies, 2023)

Recent trends in material design and preparation with structure-activity relationship for gold recovery from E-waste: A review - Mudasir Ahmad; Tariq Shah; Muhammad Rizwan Tariq; Lei Zhang; Yanting Lyu; Waheed Iqbal; Mehraj ud-din Naik; Ajit Khosla; Qiuyu Zhang; Baoliang Zhang (Journal of Cleaner Production, 2023)

Spatial distribution of potentially toxic elements contaminations and risk indices of water and sediments in the Darband and Samana streams, Pakistan - Imran Ud Din; Said Muhammad; Inayat ur Rehman; Cem Tokatli (Environmental Monitoring and Assessment, 2023)

Multiple design and modelling approaches for the optimisation of carbon felt electro-Fenton treatment of dye laden wastewater - Hammad Khan; Sajjad Hussain; Muhammad Amad Ud Din; Muhammad Arshad; Fazal Wahab; Usman Hassan; Abad Khan (Chemosphere, 2023)

Enhancing efficiency of biological contact oxidation reactors through filaments optimization of basalt fibers bio-carriers: Insights from a pilot-scale study - Huicheng Ni; Muhammad Arslan; Tiancai Zhang; Lizhuang Chen; Yaping Wang; Junchao Qian; Fu Cao; Zhiren Wu; Mohamed Gamal El-Din (Journal of Water Process Engineering, 2023)

Synthesis of MXene-based single-atom catalysts for energy conversion applications - Muhammad Aizaz Ud Din; Syed Shoaib Ahmad Shah; Muhammad Sufyan Javed; Manzar Sohail; Aziz ur Rehman; Muhammad Altaf Nazir; Mohammed A. Assiri; Tayyaba Najam; Nanpu Cheng (Chemical Engineering Journal, 2023)

Comparative evaluation of different moulting methods on productive performance, egg quality, and antibody response of leghorn hens - Amir Saeed; Shahid Mehmood; Muhammad Shahid Zahoor; Ehsaan Ullah Khan; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi; Kinza Saleem; Sohail Ahmad (Tropical Animal Health and Production, 2023)

Effects of different fat replacers on functional and rheological properties of low-fat mozzarella cheeses: A review - Aqsa Akhtar; Iqra Nasim; Muhammad Saeed ud Din; Tetsuya Araki; Nauman Khalid (Trends in Food Science & Technology, 2023)

Smart reprogramming of jujube germplasm against salinity tolerance through molecular tools - Meryam Manzoor; Safina Naz; Hafiza Muniba Din Muhammad; Riaz Ahmad (Functional & Integrative Genomics, 2023)

Role of pretreatment type and microbial mechanisms on enhancing volatile fatty acids production during anaerobic fermentation of refinery waste activated sludge - Qinghong Wang; Wenzhuo Xin; Zhiguo Shao; Muhammad Usman; Jin Li; Pengyin Shang; Yue Kou; Mohamed Gamal El-Din; Chunmao Chen (Bioresource Technology, 2023)

A modified experimental approach to determine formation porosity from rock cuttings - Semab Tariq; Zeeshan Khan; Allah Bakhsh; Syed Jamal ud Din; Azizullah Shaikh; Habib Ur Rehman; Rashid Sher Muhammad; Liang Zhang (Arabian Journal of Geosciences, 2023)

Isolation of two new triterpene glycoside from the fruits of Terminalia arjuna and their in vitro and in silico studies - Rashadul Hossain; Rajia Sultana; Md. Din Islam; Shahed Zaman; Muhammad Iqbal Choudhary (Natural Product Research, 2023)

Performance of constructed floating wetlands in a cold climate waste stabilization pond - Muhammad Arslan; Sarah Wilkinson; M. Anne Naeth; Mohamed Gamal El-Din; Zimran Khokhar; Christopher Walker; Terry Lucke (Science of The Total Environment, 2023)

Application of portable Vis-NIR spectroscopy for rapid detection of myoglobin in frozen pork - Yanna Rong; Muhammad Zareef; Lihua Liu; Zia Ud Din; Quansheng Chen; Qin Ouyang (Meat Science, 2023)

Soil organic carbon sequestration and modeling under conservation tillage and cropping systems in a rainfed agriculture - Sana ur Rehman; Shahzada Sohail Ijaz; Muhammad Ali Raza; Atta Mohi Ud Din; Khalid Saifullah Khan; Shroz Fatima; Taqi Raza; Sajid Mehmood; Amjad Saeed; Muhammad Ansar (European Journal of Agronomy, 2023)

Modelling the ingress and charge enhanced deposition behaviour of radioactive aerosols in dwellings - Tashfeen Muhammad Hammad Ud Din; Miriam A. Byrne; James A. McGrath (Atmospheric Environment, 2023)

Epidemiological survey of bovine gammaherpesvirus 4 (BoHV-4) infection in cattle and buffalo from Pakistan - Anees Khalid; Aayesha Riaz; Arfan Yousaf; Irtaza Hassan Khan; Saif Ur-Rehman; Muhammad Moaeen-ud-Din; Song Li; Congli Tang; Muhammad Ali Shah; Murtaz-ul-Hasan (Veterinary Research Communications, 2023)

Current Status of Coral Reef Fish Abundances at Pulau Bidong and Nearby Islands, South China Sea Using Stereo-Diver Operated Video System - Aminudin Muhammad Afiq-Firdaus; Che Din Mohd Safuan; Suhaidi Shafie; Lila Iznita Izhar; Ezmahamrul Afreen Awalludin; Muhammad Faiz Ahmad; Nur Arbaeen Mohd Johari; Zainudin Bachok (Ocean Science Journal, 2023)

In-field deployable and facile nanosensor for the detection of pesticides residues - Naveed Akhtar Shad; Anam Munawar; Yasir Javed; Allah Rakha; Ahsan Riaz; Salah Ud Din; Iqra Zareef; Muhammad Munir Sajid; Muahmmad Farhan Khan; Sareen Akhtar; Midhat Salman (Analytica Chimica Acta, 2023)

Heavy metal(loid)s contaminations in soils of Pakistan: a review for the evaluation of human and ecological risks assessment and spatial distribution - Imran Ud Din; Said Muhammad; Inayat ur Rehman (Environmental Geochemistry and Health, 2023)

Chitosan Polymerized Silica Composite as a Potential Silicon Source: Modulation on Antioxidant Enzymes, Ionic Homeostasis, and Grain Quality in Maize Plants Under Na+ Stress - Waqas-ud-Din Khan; Faiza Sharif; Muhammad Asif Naeem; Muhammad Ansar Farooq; Zafar Siddiq; Muhammad Imran (Journal of Plant Growth Regulation, 2023)

Methods to convert lignocellulosic waste into biohydrogen, biogas, bioethanol, biodiesel and value-added chemicals: a review - Nalok Dutta; Muhammad Usman; Muhammad Awais Ashraf; Gang Luo; Mohamed Gamal El-Din; Shicheng Zhang (Environmental Chemistry Letters, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Inter-specific root interactions and water use efficiency of maize/soybean relay strip intercropping - Xiao Te; Atta Mohi Ud Din; Kuoshu Cui; Muhammad Ali Raza; Muhammad Fraz Ali; Jiahui Xiao (Field Crops Research, 2023)

Fate of dissolved organics and generated sulfate ions during biofiltration of oil sands process water pretreated with sulfate radical advanced oxidation process - Muhammad Arslan; Soliu O. Ganiyu; Dustin M.E. Lillico; James L. Stafford; Mohamed Gamal El-Din (Chemical Engineering Journal, 2023)

Chemotaxonomy of reef building corals (family: Acroporidae) via fatty acid biomarkers - Che Din Mohd Safuan; Hock Seng Tan; Muhammad Arif Samshuri; Aminudin Muhammad Afiq-Firdaus; Zainudin Bachok (Biochemical Systematics and Ecology, 2023)

A comparative study of different types of the inversion algorithms for the reservoir characterization of Mehar Block, Pakistan - Nizam Ud Din; Muhammad Kashif; Jamil Khan; Zaheer Hussain; Jose N. Mendez; Wasif Saeed (Arabian Journal of Geosciences, 2023)

An integrated investigation of hydrocarbon pollution in Ahoada area, Niger Delta Region, Nigeria - Hafiz Aminu Umar; Mohd Faisal Abdul Khanan; Mohammed Sanusi Shiru; Anuar Ahmad; Muhammad Zulkarnain Abdul Rahman; Ami Hassan Md din (Environmental Science and Pollution Research, 2023)

Assessment of aflatoxin M 1 exposure and associated determinants in children from Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Fareeha Akhtar; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2023)

Polyelectrolyte multilayers coating of aliphatic polyamide anion-exchange membranes to increase monovalent/divalent anions selectivity in electrodialysis - Muhammad Ahmad; Mahmood Ahmed; Shabbir Hussain; Abid Ali; Manzar Zahra; Muhammad Imran Din; Zeeshan Mustafa (Desalination, 2023)

Correction to: Eco-friendly strategies for the management of Curvularia spicifera through phytobiocides and biological antagonists - Palwasha; Siraj ud Din; Muhammad Fahim (European Journal of Plant Pathology, 2023)

Efficacy of cow and buffalo dung on vermiremediation and phytoremediation of heavy metals via Fourier-transform infrared spectroscopy and comet assay - Anum Naseer; Saiqa Andleeb; Abdul Basit; Shaukat Ali; Muhammad Siraj ud-Din; Nazish Mazhar Ali; Iram Liaqat; Aisha Nazir (Environmental Science and Pollution Research, 2022)

Heavy metal(loid)s contamination and potential risk assessment via groundwater consumption in the district of Hangu, Pakistan - Imran Ud Din; Said Muhammad; Shah Faisal; Inayat ur Rehman; Wajid Ali (Environmental Science and Pollution Research, 2022)

Identification and primary distribution of Citrus viroid V in citrus in Punjab, Pakistan - Amjad Ali; Ummad ud din Umar; Sohail Akhtar; Muhammad Taimoor Shakeel; Ateeq ur Rehman; Muhammad Nouman Tahir; Sagheer Atta; Mahmoud Moustafa; Fatih Ölmez; Rashida Parveen (Molecular Biology Reports, 2022)

Eco-friendly strategies for the management of Curvularia spicifera through phytobiocides and biological antagonists - Palwasha; Siraj ud Din; Muhammad Fahim (European Journal of Plant Pathology, 2022)

First report of cucumber-infecting cucurbit chlorotic yellows virus (CCYV) associated with cucurbit yellows disease in Pakistan - Muhammad Nouman; Tahir Farooq; Rashida Parveen; Ummad ud-Din Umar; Muhammad Naveed Aslam; Mahmoud Moustafa; Muhammad Taimoor Shakeel (Journal of Plant Pathology, 2022)

Human health risk estimation of antibiotics transferred from wastewater and soil to crops - Nazish Mohy-u-Din; Muhammad Farhan; Abdul Wahid; Lena Ciric; Faiza Sharif (Environmental Science and Pollution Research, 2022)

Evaluation of agro-morphological traits, seed characterization and genetic diversity of local rice (Oryza sativa L.) varieties of Pakistan - Urooj Fazal; Israr Ud Din; Amir Muhammad Khan; Fahim Ullah Khan; Mudassar Nawaz Khan; Navid Iqbal; Muhammad Ibrahim; Sajid Ali Khan Bangash (Genetic Resources and Crop Evolution, 2022)

Hybrid geoid model over peninsular Malaysia (PMHG2020) using two approaches - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Ramazan Alpay Abbak; Mohammad Hanif Hamden; Nornajihah Mohammad Yazid; Mohamad Azril Che Aziz; Mohd Adhar Abd Samad (Studia Geophysica et Geodaetica, 2022)

Side-Scan Sonar Coupled with Scuba Diving Observation for Enhanced Monitoring of Benthic Artificial Reefs along the Coast of Terengganu, Peninsular Malaysia - Azizi Ali; Muhammad Ruzi Abdullah; Che Din Mohd Safuan; Aminudin Muhammad Afiq-Firdaus; Zainudin Bachok; Mohd Fadzil Mohd Akhir; Roslan Latif; Azri Muhamad; Tan Hock Seng; Adina Roslee; Khaira Ismail (Journal of Marine Science and Engineering, 2022)
Since the 1970s, artificial reef (AR) deployment has been one of the common approaches to augment the local production of coastal fish in Malaysia. However, there is a lack of strategy to assess and evaluate the success of pre-deployed AR. Realizing the need for an effective qualitative and quantitative monitoring and evaluation of AR, this study proposes side-scan sonar coupled with scuba diving observation for the enhanced monitoring of pre-deployed Bioceramic Korean (BK) AR along the coast of Terengganu, Peninsular Malaysia. This method employs an integrated side-scan sonar with a data acquisition system for the detection of the precise location of the BK AR which were deployed at Tukun Telaga Batin off the Terengganu coastline in 2003 by the Fisheries Development Authority of Malaysia (FDAM). Following the determination of the exact location of three BK AR areas, a scuba diving team was sent to survey the physical conditions of the AR and assess the feasibility of the AR as an artificial habitat for marine life. The scan sonar images were compared with the captured photographs and videos acquired during the scuba diving session for a comprehensive value-added assessment. The collected data from the scuba diving session were also processed to measure the fish diversity, the fish biomass, and identify the fish community surrounding the AR. Based on the results, the BK AR remained in extremely good condition, physically intact, without significant breakage or damage, and with no major subsidence into the sediment after 19 years of deployment. A total of 108 BK AR modules were detected in three large groups using the mosaicked sonar images. Following cross-examination to validate the AR measurements using the AR’s shadows on the seafloor, the height of the BK AR consistently ranged from 1.7 m to 1.8 m. In addition, 34 species of fish from 14 families and 26 genera were identified, with most species classified as reef-associated (RA) fish with a biomass value of 1173.31 ± 1136.69 kg m−3, indicating the successfulness of the BK AR as fish-aggregating devices (FADs). The growth of hard corals on top of the bioceramic plate of the AR module further supported the diversified community of marine life surrounding the BK AR. In conclusion, the side-scan sonar coupled with scuba diving observation demonstrates an effective qualitative and quantitative technique for the monitoring and evaluation of pre-deployed AR. This strategy is recommended to be utilized to determine the success of pre-deployment AR.

Antileishmanial Agents Co-loaded in Transfersomes with Enhanced Macrophage Uptake and Reduced Toxicity - Fatima Zahid; Sibgha Batool; Fakhar ud-Din; Zakir Ali; Muhammad Nabi; Salman Khan; Omer Salman; Gul Majid Khan (AAPS PharmSciTech, 2022)

Assessment of aflatoxin B 1 -lysine adduct in children and its effect on child growth in Lahore, Pakistan - Waseela Ashraf; Abdul Rehman; Mansur-ud-Din Ahmad; Masood Rabbani; Muhammad Hassan Mushtaq; Khalida Aamir; Kathy S. Xue; Jia-Sheng Wang (Food Additives & Contaminants: Part A, 2022)

Improving the Accuracy of Local Gravimetric Geoid Modelling Using Simulated Terrestrial Gravity Data - Shazad Jamal Jalal; Tajul Ariffin Musa; Ami Hassan Md Din; Wan Anom Wan Aris; Muhammad Faiz Pa’suya (Pure and Applied Geophysics, 2022)

Sargassum wightii Aqueous Extract Improved Salt Stress Tolerance in Abelmoschus esculentus by Mediating Metabolic and Ionic Rebalance - Zawar Khan; Humaira Gul; Mamoona Rauf; Muhammad Arif; Muhammad Hamayun; Aziz Ud-Din; Zahoor Ahmad Sajid; Sheza Ayaz Khilji; Aliya Rehman; Asma Tabassum; Zahida Parveen; In-Jung Lee (Frontiers in Marine Science, 2022)
Salinity stress has hindered the growth and yield of crops globally. The demands for inducing salt stress tolerance by natural and biological sources with potent antioxidants and growth-promoting metabolites have been the main focus of the recent era. Therefore, the current research was conducted to extract salt stress tolerance-ameliorating metabolites and growth-promoting hormones from the marine brown macroalgae Sargassum wightii Greville ex J. Agardh with maximum antioxidant potential used as a liquid fertilizer for okra ( Abelmoschus esculentus L.). In the current study, the biochemical analysis showed that Sargassum aqueous extract (SAE) was rich in growth-promoting metabolites, antioxidants, and hormones. Meanwhile, overaccumulation of glycine betaine attracted the focus of the current research dealing with salt stress tolerance amelioration in A. esculentus . The plants supplemented with SAE (2% and 4%) and 0.04% ascorbic acid (AsA) alone and in combinations were subjected to sodium salt stress (NaCl; 75 mM). Results revealed that SAE efficiently promoted the vegetative and reproductive growth of plants by elevating the growth-promoting metabolites and hormones in comparison to control plants. Ionic contents (Na + , K + , Ca 2+ , and Mg 2+ ) and ratios (K + /Na + , Mg 2+ /Na + , and Ca 2+ /Na + ) were modulated in SAE-treated plants. SAE also increased the level of carbohydrates, proteins, lipids, carotenoids, and proline and decreased the level of hydrogen peroxide and abscisic acid in salt-treated plants compared with the control groups. Enzymatic activities of catalase, ascorbate peroxidase, and guaiacol peroxidase were also enhanced by SAE treatment upon salt stress. The SAE-mediated stress tolerance amelioration and the positive growth response of A. esculentus were further accelerated by AsA (0.04%) supplementation used in combination with SAE (2% and 4%). The current study revealed a novel report of the antioxidant and metabolite-rich algal extract ( S. wightii ) formulation along with AsA that induced salt stress tolerance and promoted the overall growth performance of A. esculentus by rebalancing the ionic and metabolic status.

Prevalence, transmission and molecular characterization of Cotton leaf curl Multan virus infecting hollyhock plants in Pakistan - Hajra Azeem; Rashida Perveen; Muhammad Nouman Tahir; Ummad-ud-din Umar; Fatih Ölmez; Amjad Ali (Molecular Biology Reports, 2022)

Intelligent autonomous underwater vehicle mobility with energy efficient routing in sensor networks - Imran Shafi; Muhammad Junaid Ashraf; Gyu Sang Choi; Sadia Din; Imran Ashraf (Environment, Development and Sustainability, 2022)

Effects of mirror and coloured balls as environmental enrichment tools on performance, welfare and meat quality traits of commercial broiler - Muhammad Shahid Zahoor; Sohail Ahmad; Muhammad Usman; Muhammad Dawood; Karim El-Sabrout; Syed Ghulam Mohayud Din Hashmi; Ehsaan Ullah Khan; Murrawat Hussain; Muhammad Adeel Maqsood; Hafiz Rao Abdul Latif (Tropical Animal Health and Production, 2022)

Baseline toxicity of ten insecticides from organophosphate, pyrethroid and novel mode of action groups against Droschica mangiferae (Homoptera: Margarodidae) collected from citrus orchard in 2017–19 - Muhammad Nawaz Khan; Muhammad Babar Shahzad Afzal; Naima Din; Afifa Naeem; Ansa Banazeer; Malik Abdul Rehman; Hira Tariq; Muhammad Raza Salik; Muhammad Qasim (International Journal of Tropical Insect Science, 2022)

Applications of Biotechnology in Food and Agriculture: a Mini-Review - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Waseem Khalid; Hafiz Rehan Nadeem; Ghulam Mueen-ud-Din; Muhammad Zubair Khalid (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Economic and financial impact of the COVID-19 pandemic in South Asia - Muhammad Azhar Khan; Hasnain Abbas Naqvi; Muhammad Mohsin Hakeem; Ghulam Moeen ud Din; Nadeem Iqbal (Environmental Science and Pollution Research, 2022)

Structural characterization and antileishmanial activity of newly synthesized organo-bismuth(V) carboxylates: experimental and molecular docking studies - Sohaila Andleeb; Imtiaz-ud-Din; Muhammad Khawar Rauf; Syed Sikander Azam; Ihsan‐ul Haq; Muhammad Nawaz Tahir; Naila Zaman (JBIC Journal of Biological Inorganic Chemistry, 2022)

Green bond as a new determinant of sustainable green financing, energy efficiency investment, and economic growth: a global perspective - Yiyi Ning; Jacob Cherian; Muhammad Safdar Sial; Susana Álvarez-Otero; Ubaldo Comite; Malik Zia-Ud-Din (Environmental Science and Pollution Research, 2022)

A Review of Antimicrobial Peptides: Its Function, Mode of Action and Therapeutic Potential - Sehrish Nayab; Muhammad Aamir Aslam; Sajjad ur Rahman; Zia ud Din Sindhu; Sanaullah Sajid; Nishat Zafar; Maida Razaq; Rabia Kanwar; Amanullah (International Journal of Peptide Research and Therapeutics, 2022)

Soil microbial biomass and extracellular enzyme–mediated mineralization potentials of carbon and nitrogen under long-term fertilization (> 30 years) in a rice–rice cropping system - Muhammad Nadeem Ashraf; Gao Jusheng; Wu Lei; Adnan Mustafa; Ahmed Waqas; Tariq Aziz; Waqas-ud-Din Khan; Shafeeq-ur-Rehman; Babar Hussain; Muhammad Farooq; Zhang Wenju; Xu Minggang (Journal of Soils and Sediments, 2021)

Essential oil composition and antibacterial activity of Canarium strictum Roxb. resin - Halima Tahir; Nadeem Muhammad; Azeem Intisar; Muhammad Imran Din; Uzma Qaisar; Muhammad Abdul Qadir; Noor Ul Ain; Zeeshan Ahmad; Pakeeza Aziz; Muhammad Khurram Shahzad; Irshad Hussain (Plant Biosystems, 2021)

Constituents and antibacterial activity of leaf essential oil of Plectranthus scutellarioides - Pakeeza Aziz; Nadeem Muhammad; Azeem Intisar; Muhammad Amin Abid; Muhammad Imran Din; Muhammad Yaseen; Rehana Kousar; Aqsa Aamir; Quratulain; Rabia Ejaz (Plant Biosystems, 2021)

Quantile nexus between human development, energy production, and economic growth: the role of corruption in the case of Pakistan - Muhammad Luqman; Yafei Li; Salah Ud-Din Khan; Najid Ahmad (Environmental Science and Pollution Research, 2021)

Occurrence, distribution, and pollution indices of potentially toxic elements within the bed sediments of the riverine system in Pakistan - Javed Nawab; Zia Ud Din; Riaz Ahmad; Sardar Khan; Mazhar Iqbal Zafar; Shah Faisal; Waleed Raziq; Hamza Khan; Zia Ur Rahman; Abid Ali; Muhammad Qayash Khan; Sajid Ullah; et al. (Environmental Science and Pollution Research, 2021)

Refinement of gravimetric geoid model by incorporating terrestrial, marine, and airborne gravity using KTH method - Muhammad Faiz Pa’suya; Ami Hassan Md Din; Mohd Yunus Mohd Yusoff; Ramazan Alpay Abbak; Mohammad Hanif Hamden (Arabian Journal of Geosciences, 2021)

Physiological Response of Shallow-Water Hard Coral Acropora digitifera to Heat Stress via Fatty Acid Composition - Che Din Mohd Safuan; Muhammad Arif Samshuri; Siti Nurtahirah Jaafar; Chun Hong Tan; Zainudin Bachok (Frontiers in Marine Science, 2021)
Heat stress disturbs the mutualistic relationship between the hard corals and the symbiotic algae, which cause coral bleaching. A wide array of biochemical parameters is used to demonstrate the phenomenon. This study exposed a shallow-water hard coral, Acropora digitifera , to a series of elevated temperatures over time while the interaction between Symbiodiniaceae (SD) density, antioxidants activities, fatty acid (FA) composition, and putative FA health indicators was evaluated. Heat stress caused a substantial loss in SD densities, consequently regulated the antioxidant activities and caused significant changes in FA composition. There was a lack of evidence showing A. digitifera experienced oxidative stress; nonetheless, a significant decrease of monounsaturated fatty acid as (MUFA) and polyunsaturated fatty acid (PUFA) during the thermally induced experiment demonstrated that corals utilize their unsaturated FA as a final barrier or as a repair system against oxidative damage once the antioxidant enzyme cannot cope with stress condition. The lower ratio of putative FA health indicators [i.e., n-3 LC:n-6 LC, eicosapentaenoic acid (EPA):arachidonic acid (ARA), and docosahexaenoic acid (DHA):ARA] characterized an unhealthy coral. The loss of SD density was significantly correlated with certain PUFA markers [i.e., linolenic acid (18:3n6), 20:5n3, and 22:6n3] and putative FA health indicator (i.e., n-3 LC:n-6 LC, EPA:ARA, and DHA:ARA). These notably imply that the FA linked with the symbiont can be a potential health indicator for assessing the effect of the environmental stressor on coral. This study also revealed the regulation of FAs during stress conditions, especially when heterotrophic feeding is limited. Future studies on FA profiles toward antagonistic or synergistic effects will offer a better understanding of the nature of this relationship under a harsh climate.

The Transition from Arid Farming Systems to Agroforestry Systems in Pakistan: A Comparison of Monetary Returns - Ghulam Abbas; Akhter Ali; Muhammad Khan; Hafiz Zahid Mahmood; Sazali Abdul Wahab; Rafi Amir-ud-Din (Small-scale Forestry, 2021)

Helminth protection against type-1 diabetes: an insight into immunomodulatory effect of helminth-induced infection - Muhammad Adnan Sabir Mughal; Muhammad Kasib Khan; Zaheer Abbas; Rao Zahid Abbas; Hammad ur Rehman Bajwa; Abdullah Khalid Chatha; Muhammad Imran; Zia ud Din Sindhu; Asghar Abbas; Arsalan Zafar; Muhammad Nadeem (Molecular Biology Reports, 2021)

Paclobutrazol Improves Sesame Yield by Increasing Dry Matter Accumulation and Reducing Seed Shattering Under Rainfed Conditions - Muhammad Zeeshan Mehmood; Ghulam Qadir; Obaid Afzal; Atta Mohi Ud Din; Muhammad Ali Raza; Imran Khan; Muhammad Jawad Hassan; Samrah Afzal Awan; Shakeel Ahmad; Muhammad Ansar; Muhammad Aqeel Aslam; Mukhtar Ahmed (International Journal of Plant Production, 2021)
Several biotic and abiotic stresses significantly decrease the biomass accumulation and seed yield of sesame crops under rainfed areas. However, plant growth regulators (such as Paclobutrazol) can improve the total dry matter and seed production of the sesame crop. The effects of the paclobutrazol application on dry matter accumulation and seed yield had not been studied before in sesame under rainfed conditions. Therefore, a two-year field study during 2018 and 2019 was conducted with key objectives to assess the impacts of paclobutrazol on leaf greenness, leaf area, total dry matter production and partitioning, seed shattering, and seed yield of sesame. Two sesame cultivars (TS-5 and TS-3) were treated with four paclobutrazol concentrations (P0 = Control, P1 = 100 mg L −1 , P2 = 200 mg L −1 , P3 = 300 mg L −1 ). The experiment was executed in RCBD-factorial design with three replications. Compared with P0, treatment P3 improved the leaf greenness of sesame by 17%, 38%, and 60% at 45, 85, and 125 days after sowing, respectively. However, P3 treatment decreased the leaf area of sesame by 14% and 20% at 45 and 85 days after sowing than P0, respectively. Compared with P0, treatment P3 increased the leaf area by 46% at 125 days after sowing. On average, treatment P3 also improved the total biomass production by 21% and partitioning in roots, stems, leaves, capsules, and seeds by 23%, 19%, 23%, 22%, and 40%, respectively, in the whole growing seasons as compared to P0. Moreover, under P3 treatment, sesame attained the highest seed yield and lowest seed shattering by 27% and 30%, respectively, compared to P0. This study indicated that by applying the paclobutrazol concentration at the rate of 300 mg L −1 in sesame, the leaf greenness, leaf areas, biomass accumulation, partitioning, seed yield, and shatter resistance could be improved. Thus, the optimum paclobutrazol level could enhance the dry matter accumulation and seed production capacity of sesame by decreasing shattering losses under rainfed conditions.

Origin, Pathogenesis, Diagnosis and Treatment Options for SARS-CoV-2: A Review - Humna Sajjad; Mohsin Majeed; Saiqa Imtiaz; Mariyam Siddiqah; Anila Sajjad; Misbahud Din; Muhammad Ali (Biologia, 2021)

Petro-physical evaluation and identifying possible resource plays using the porosity and resistivity logs, Lower Indus Basin, Pakistan - Nizam Ud Din; Zhang Hongbing; Muhammad Kashif; Wasif Saeed (Arabian Journal of Geosciences, 2021)

Correction to: Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Phytoremediation Potential of E. camaldulensis and M. alba for Copper, Cadmium, and Lead Absorption in Urban Areas of Faisalabad City, Pakistan - Ghulam Yasin; Shafeeq Ur Rahman; Muhammad Talha Bin Yousaf; Muhammad Farooq Azhar; Din Muhammad Zahid; Muhammad Imtiaz; Babar Hussain (International Journal of Environmental Research, 2021)

Compact maize canopy improves radiation use efficiency and grain yield of maize/soybean relay intercropping system - Muhammad Ali Raza; Liang Cui; Imran Khan; Atta Mohi Ud Din; Guopeng Chen; Muhammad Ansar; Mukhtar Ahmed; Shakeel Ahmad; Abdul Manaf; John Kwame Titriku; Ghulam Abbas Shah; Feng Yang; et al. (Environmental Science and Pollution Research, 2021)

COVID-19 transmission, vulnerability, persistence and nanotherapy: a review - Afzal Husain Khan; Vineet Tirth; Manal Fawzy; Alaa El Din Mahmoud; Nadeem A. Khan; Sirajuddin Ahmed; Syed Sadat Ali; Muhammad Akram; Leena Hameed; Saiful Islam; Gotam Das; Sharmili Roy; et al. (Environmental Chemistry Letters, 2021)

Exploring genetic diversity and population structure of Punjab goat breeds using Illumina 50 K SNP bead chip - Raja Danish Muner; Muhammad Moaeen-ud-Din; Ghulam Bilal; Hafiz Muhammad Waheed; Muhammad Sajjad Khan; Muhammad Javaid Asad; Zulfiqar Hussain Kuthu (Tropical Animal Health and Production, 2021)

Can sulphur improve the nutrient uptake, partitioning, and seed yield of sesame? - Muhammad Zeeshan Mehmood; Obaid Afzal; Mukhtar Ahmed; Ghulam Qadir; Ahmed M.S. Kheir; Muhammad Aqeel Aslam; Atta Mohi Ud Din; Imran Khan; Muhammad Jawad Hassan; Tehseen Ahmad Meraj; Muhammad Ali Raza; Shakeel Ahmad (Arabian Journal of Geosciences, 2021)
Sulphur (S) is considered to improve the nutrient uptake of plants due to its synergistic relationship with other nutrients. This could ultimately enhance the seed yield of oilseed crops. However, there is limited quantitative information on nutrient uptake, distribution, and its associated impacts on seed yield of sesame under the S application. Thus, a two-year field study (2018 and 2019) was conducted to assess the impacts of different S treatments (S 0 = Control, S 20 = 20, S 40 = 40, and S 60 = 60 kg ha −1 ) on total dry matter production, nitrogen, phosphorus, potassium, S uptake and distribution at the mid-bloom stage and physiological maturity. Furthermore, treatment impacts were studied on the number of capsules per plant, number of seeds per capsule, thousand seed weight, and seed yield at physiological maturity in sesame. Compared to S 0 , over the years, treatment S 40 significantly increased the total uptake of nitrogen, phosphorus, potassium, and S (by 13, 22, 11% and 16%, respectively) at physiological maturity, while their distribution by 13, 36, 14, and 24% (in leaves), 12, 15, 11, and 15% (in stems), 15, 42, 18, and 10% (in capsules), and 14, 22, 9, and 15% (in seeds), respectively. Enhanced nutrient uptake and distribution in treatment S 40 improved the total biomass accumulation (by 28%) and distribution in leaves (by 34%), stems (by 27%), capsules (by 26%), and seeds (by 28%), at physiological maturity, as compared to S 0 . Treatment S 40 increased the number of capsules per plant (by 13%), number of seeds per capsule (by 11%), and thousand seed weight (by 6%), compared to S 0 . Furthermore, over the years, relative to control, sesame under S 40 had a higher seed yield by 28% and enhanced the net economic returns by 44%. Thus, our results suggest that optimum S level at the time of sowing improves the nutrient uptake and distribution during the plant lifecycle, which ultimately enhances total dry matter accumulation, seed yield, and net productivity of sesame.

Geospatially mapping carbon stock for mountainous forest classes using InVEST model and Sentinel-2 data: a case of Bagrote valley in the Karakoram range - Muhammad Imran; Noor ud Din (Arabian Journal of Geosciences, 2021)

Development of broad-spectrum and sustainable resistance in cotton against major insects through the combination of Bt and plant lectin genes - Salah ud Din; Saira Azam; Abdul Qayyum Rao; Mohsin Shad; Mukhtar Ahmed; Ambreen Gul; Ayesha Latif; Muhammad Azam Ali; Tayyab Husnain; Ahmad Ali Shahid (Plant Cell Reports, 2021)

The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Correction to: The antioxidant N-(2-mercaptopropionyl)-glycine (tiopronin) attenuates expression of neuropathic allodynia and hyperalgesia - Muhammad Shahid; Fazal Subhan; Nazar Ul Islam; Nisar Ahmad; Umar Farooq; Sudhair Abbas; Shehla Akbar; Ihsan Ullah; Naila Raziq; Zia Ud Din (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Influence of semi-arid environment on radiation use efficiency and other growth attributes of lentil crop - Muhammad Habib ur Rahman; Ishfaq Ahmad; Depeng Wang; Shah Fahad; Muhammad Afzal; Abdul Ghaffar; Qaisar Saddique; Mehmood Alam Khan; Shah Saud; Shah Hassan; Muhammad Fahad; Mairaj Din; et al. (Environmental Science and Pollution Research, 2021)

Chemiluminescent-microparticle-immunoassay-based detection and prevalence of human immunodeficiency virus infection in Islamabad, Pakistan - Misbahud Din; Faheem Anwar; Muhammad Ali; Muhammad Yousaf; Bilal Ahmad; Abdullah (Archives of Virology, 2021)

Influence of indigenous plant materials on reproductive performance of Callosobruchus chinensis (L.) (Coleoptera: Bruchidae) on chickpea - Bilawal Nizamani; Mushtaque Ahmed Agha; Qurban Ali; Amjad Hussain; Hakim Manghwar; Muhammad Kamran; Aafaque Ahmed Keerio; Zeeshan Ahmed Solangi; Muhammad Akbar Lashari; Din Muhammad Soomro (International Journal of Tropical Insect Science, 2020)

Potentially toxic elements’ occurrence and risk assessment through water and soil of Chitral urban environment, Pakistan: a case study - Inayat ur Rehman; Muhammad Ishaq; Liaqat Ali; Said Muhammad; Imran Ud Din; Muhammad Yaseen; Hameed Ullah (Environmental Geochemistry and Health, 2020)

Mo-Inefficient Wheat Response Toward Molybdenum Supply in Terms of Soil Phosphorus Availability - Muhammad Shoaib Rana; Xuecheng Sun; Muhammad Imran; Zaid Khan; Mohamed G. Moussa; Muhammad Abbas; Parashuram Bhantana; Muhamad Syaifudin; Intisar Ud Din; Muhammad Younas; Md Ashrafuzzaman Shah; Javaria Afzal; et al. (Journal of Soil Science and Plant Nutrition, 2020)

A novel approach for high-level expression and purification of GST-fused highly thermostable Taq DNA polymerase in Escherichia coli - Rahman Ud Din; Muhammad Ismail Khan; Asad Jan; Shah Anwar Khan; Irshad Ali (Archives of Microbiology, 2020)

Bisphenol-A induced antioxidants imbalance and cytokines alteration leading to immune suppression during larval development of Labeo rohita - Mehwish Faheem; Muhammad Adeel; Saba Khaliq; Khalid P. Lone; Alaa El-Din-H-Sayed (Environmental Science and Pollution Research, 2020)

Pigment production by cold-adapted bacteria and fungi: colorful tale of cryosphere with wide range applications - Wasim Sajjad; Ghufranud Din; Muhammad Rafiq; Awais Iqbal; Suliman Khan; Sahib Zada; Barkat Ali; Shichang Kang (Extremophiles, 2020)

Single or Combined Applications of Zinc and Multi-strain Probiotic on Intestinal Histomorphology of Broilers Under Cyclic Heat Stress - Muqader Shah; Hafsa Zaneb; Saima Masood; Rifat Ullah Khan; Muhammad Mobashar; Imad Khan; Salahud Din; Muhammad Shoaib Khan; Habib Ur Rehman; Antonella Tinelli (Probiotics and Antimicrobial Proteins, 2020)

Production analysis of broiler farming in central Punjab, Pakistan - Naeem Ur Rahman; Shahid Mehmood; Sohail Ahmad; Arshad Javid; Athar Mahmud; Jibran Hussain; Muhammad Shabir Shaheen; Muhammad Usman; Syed Ghulam Mohayud Din Hashmi (Tropical Animal Health and Production, 2020)

Potential perspectives of biodegradable plastics for food packaging application-review of properties and recent developments - Muhammad Imran Din; Tayabba Ghaffar; Jawayria Najeeb; Zaib Hussain; Rida Khalid; Hafsa Zahid (Food Additives & Contaminants: Part A, 2020)

Copper-induced oxidative stress, initiation of antioxidants and phytoremediation potential of flax (Linum usitatissimum L.) seedlings grown under the mixing of two different soils of China - Muhammad Hamzah Saleem; Shah Fahad; Shahid Ullah Khan; Mairaj Din; Abid Ullah; Ayman EL Sabagh; Akbar Hossain; Analía Llanes; Lijun Liu (Environmental Science and Pollution Research, 2020)

DNA barcoding of Haplophyllum gilesii (Hemsel.) C. C. Townsend from the Gilgit-Baltistan Province of Pakistan - Bushra Khan; Habib Ahmad; Jan Alam; Muhammad Shahid Nadeem; Aziz Ud-Din; Inam Ullah; Shafee Ur Rehman; Khushi Muhammad (Brazilian Journal of Botany, 2019)

First detection and molecular characterization of avian polyomavirus in young parrots in Pakistan - Aayesha Riaz; Arfan Yousaf; Muhammad Moaeen-ud-Din; Muhammad Ali Abdullah Shah; Tayyaba Zainab; Sadia Masood; Naeem Akhter; Adnan Ali (Veterinary Research Communications, 2019)

Effect of feeding different levels of discarded date palm (Phoenix dactylifera) on digestibility, milk yield, and composition in Damani sheep - Naveed Iqbal; Muhammad Tahir Khan; Haq Amanullah; Israru Din; Hamayun Khan; Muqader Shah; Muhammad Mushtaq (Tropical Animal Health and Production, 2019)

Development and Evaluation of Optimized Thiolated Chitosan Proniosomal Gel Containing Duloxetine for Intranasal Delivery - Maryam khatoon; Muhammad Farhan Sohail; Gul Shahnaz; Fiza ur Rehman; Fakhar-ud-Din; Asim ur Rehman; Naseem Ullah; Umair Amin; Gul Majid Khan; Kifayat Ullah Shah (AAPS PharmSciTech, 2019)

Vulnerability, well-being, and livelihood adaptation under changing environmental conditions: a case from mountainous region of Pakistan - Laila Shahzad; Arifa Tahir; Faiza Sharif; Waqas Ud Din Khan; Muhammad Ansar Farooq; Azhar Abbas; Zulfiqar Ahmad Saqib (Environmental Science and Pollution Research, 2019)

Identification and characterization of dwarf mistletoe responding genes in Ziarat juniper tree (Juniperus excelsa M.Bieb) through suppression subtractive hybridization and deep sequencing - Humaira Abdul Wahid; Muhammad Younas Khan Barozai; Muhammad Din (Trees, 2019)

Synthesis of magnetite-based nanocomposites for effective removal of brilliant green dye from wastewater - Muhammad Imran; Azhar Ul Islam; Muhammad Adnan Tariq; Muhammad Hussnain Siddique; Noor Samad Shah; Zia Ul Haq Khan; Muhammad Amjad; Salah Ud Din; Ghulam Mustafa Shah; Muhammad Asif Naeem; Muhammad Nadeem; Muhammad Nawaz; et al. (Environmental Science and Pollution Research, 2019)

Petrology and geochemistry of dolerite and lamprophyre sills in Mesozoic successions of Khanozai–Muslim Bagh area, northwestern Pakistan - Din Muhammad; Razzaq Abdul Manan Durrani; Akhtar Muhammad Kassi; Muhammad Ishaq Kakar (Arabian Journal of Geosciences, 2019)

Effect of poultry litter biochar on chromium (Cr) bioavailability and accumulation in spinach (Spinacia oleracea) grown in Cr-polluted soil - Adiba Khan Sehrish; Rukhsanda Aziz; Muhammad Mazhar Hussain; Muhammad Tariq Rafiq; Muhammad Rizwan; Niaz Muhammad; Muhammad Khalid Rafiq; Anum Sehar; Jalal ud Din; Mohammad I. Al-Wabel; Shafaqat Ali (Arabian Journal of Geosciences, 2019)

Erosion potential assessment of watersheds through GIS-based hypsometric analysis: a case study of Kurram Tangi Dam - Wasif Yousaf; Syed Ghulam Mohayud-Din-Hashmi; Usman Akram; Urooj Saeed; Sajid Rashid Ahmad; Muhammad Umar; Ambreena Mubashir (Arabian Journal of Geosciences, 2018)

Synthesis of biochar from sugarcane filter-cake and its impacts on physiological performance of lettuce (Lettuce sativa) grown on cadmium contaminated soil - Anum Sehar; Rukhsanda Aziz; Muhammad Tariq Rafiq; Muhammad Mazhar Hussain; Muhammad Rizwan; Adiba Khan Sehrish; Muhammad Khalid Rafiq; Jalal ud Din; Qaiser Hussain; Mohammad I. Al-Wabel; Shafaqat Ali (Arabian Journal of Geosciences, 2018)

Glutamic acid assisted phyto-management of silver-contaminated soils through sunflower; physiological and biochemical response - Mujahid Farid; Shafaqat Ali; Muhammad Zubair; Rashid Saeed; Muhammad Rizwan; Rasham Sallah-Ud-Din; Ahmad Azam; Rehman Ashraf; Wasim Ashraf (Environmental Science and Pollution Research, 2018)

Sucrose synthase genes: a way forward for cotton fiber improvement - Mukhtar Ahmed; Ahmad Ali Shahid; Sidra Akhtar; Ayesha Latif; Salah ud Din; Ma Fanglu; Abdul Qayyum Rao; Muhammad Bilal Sarwar; Tayyab Husnain; Wang Xuede (Biologia, 2018)

Molecular investigation of foot-and-mouth disease virus circulating in Pakistan during 2014-17 - Waqas Ali; Mudasser Habib; Rai Shafqat Ali Khan; Muhammad Ashir Zia; Muhammad Farooq; Sanaullah Sajid; Muhammad Salah Ud Din Shah (Archives of Virology, 2018)

Correction to: Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2018)
The original article was corrected. Author Muhammad Kundi should instead read: Muhammad Sohail.

Correction to: HIV-1 genetic diversity, geographical linkages and antiretroviral drug resistance among individuals from Pakistan - Saeed Khan; Maria Zahid; Muhammad Asif Qureshi; Nouman Mughal; Ikram Din Ujjan (Archives of Virology, 2018)

HIV-1 genetic diversity, geographical linkages and antiretroviral drug resistance among individuals from Pakistan - Saeed Khan; Maria Zahid; Muhammad Asif Qureshi; Muhammad Nouman Mughal; Ikram Din Ujjan (Archives of Virology, 2018)

Influence of entomopathogenic fungus, Metarhizium anisopliae, alone and in combination with diatomaceous earth and thiamethoxam on mortality, progeny production, mycosis, and sporulation of the stored grain insect pests - Misbah Ashraf; Muhammad Farooq; Muhammad Shakeel; Naima Din; Shahbaz Hussain; Nadia Saeed; Qaiser Shakeel; Nasir Ahmed Rajput (Environmental Science and Pollution Research, 2017)

Strategic crossing of biomass and harvest index—source and sink—achieves genetic gains in wheat - Matthew P. Reynolds; Alistair J. D. Pask; William J. E. Hoppitt; Kai Sonder; Sivakumar Sukumaran; Gemma Molero; Carolina Saint Pierre; Thomas Payne; Ravi P. Singh; Hans J. Braun; Fernanda G. Gonzalez; Ignacio I. Terrile; et al. (Euphytica, 2017)
To accelerate genetic gains in breeding, physiological trait (PT) characterization of candidate parents can help make more strategic crosses, increasing the probability of accumulating favorable alleles compared to crossing relatively uncharacterized lines. In this study, crosses were designed to complement “source” with “sink” traits, where at least one parent was selected for favorable expression of biomass and/or radiation use efficiency—source—and the other for sink-related traits like harvest-index, kernel weight and grains per spike. Female parents were selected from among genetic resources—including landraces and products of wide-crossing (i.e. synthetic wheat)—that had been evaluated in Mexico at high yield potential or under heat stress, while elite lines were used as males. Progeny of crosses were advanced to the F 4 generation within Mexico, and F 4 -derived F 5 and F 6 generations were yield tested to populate four international nurseries, targeted to high yield environments (2nd and 3rd WYCYT) for yield potential, and heat stressed environments (2nd and 4th SATYN) for climate resilience, respectively. Each nursery was grown as multi-location yield trials. Genetic gains were achieved in both temperate and hot environments, with most new PT-derived lines expressing superior yield and biomass compared to local checks at almost all international sites. Furthermore, the tendency across all four nurseries indicated either the superiority of the best new PT lines compared with the CIMMYT elite checks, or the superiority of all new PT lines as a group compared with all checks, and in some cases, both. Results support—in a realistic breeding context—the hypothesis that yield and radiation use efficiency can be increased by improving source:sink balance, and validate the feasibility of incorporating exotic germplasm into mainstream breeding efforts to accelerate genetic gains for yield potential and climate resilience.

Association of chili leaf curl betasatellite with tomato leaf curl disease - Muhammad Qasim Aslam; Khalid P. Akhtar; Mohy-u-Din Akram; Muhammad Y. Saleem; Nighat Sarwar; Sumaira Yousaf (Journal of General Plant Pathology, 2017)

Bacillus safensis with plant-derived smoke stimulates rice growth under saline conditions - Muhammad Hafeez Ullah Khan; Jabar Zaman Khan Khattak; Muhammad Jamil; Ijaz Malook; Shahid Ullah Khan; Mehmood Jan; Ismail Din; Shah Saud; Muhammad Kamran; Hesham Alharby; Shah Fahad (Environmental Science and Pollution Research, 2017)

Microwave irradiation and citric acid assisted seed germination and phytoextraction of nickel (Ni) by Brassica napus L.: morpho-physiological and biochemical alterations under Ni stress - Mujahid Farid; Shafaqat Ali; Muhammad Rizwan; Rashid Saeed; Hafiz Muhammad Tauqeer; Rasham Sallah-Ud-Din; Ahmed Azam; Nighat Raza (Environmental Science and Pollution Research, 2017)

Erratum to: An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2017)

Chilling tolerance in three tomato transgenic lines overexpressing CBF3 gene controlled by a stress inducible promoter - Sabir Hussain Shah; Shaukat Ali; Abdul Ahad Qureshi; Muhammad Amir Zia; Jalal-ud -Din; Ghulam Muhammad Ali (Environmental Science and Pollution Research, 2017)

Citric acid enhanced the antioxidant defense system and chromium uptake by Lemna minor L. grown in hydroponics under Cr stress - Rasham Sallah-Ud-Din; Mujahid Farid; Rashid Saeed; Shafaqat Ali; Muhammad Rizwan; Hafiz Muhammad Tauqeer; Syed Asad Hussain Bukhari (Environmental Science and Pollution Research, 2017)

Erratum to: Cost-effective enhanced iron bioavailability in rice grain grown on calcareous soil by sulfur mediation and its effect on heavy metals mineralization - Pia Muhammad Adnan Ramzani; Muhammad Khalid; Shazia Anjum; Waqas-ud-Din Khan; Shafaqat Ali; Fakhir Hannan; Muhammad Iqbal (Environmental Science and Pollution Research, 2017)

Cost-effective enhanced iron bioavailability in rice grain grown on calcareous soil by sulfur mediation and its effect on heavy metals mineralization - Pia Muhammad Adnan Ramzani; Muhammad Khalid; Shazia Anjum; Waqas-ud-Din Khan; Shafaqat Ali; Fakhir Hannan; Muhammad Iqbal (Environmental Science and Pollution Research, 2017)

An application of AVO derived attributes to analyze seismic anomalies of gas hydrate bearing sediments in Makran offshore, Pakistan - Muhammad Irfan Ehsan; Nisar Ahmed; Zia Ud Din; Perveiz Khalid; Liu Xue Wei (Acta Geodaetica et Geophysica, 2016)

Effect of different amendments on rice (Oryza sativa L.) growth, yield, nutrient uptake and grain quality in Ni-contaminated soil - Pia Muhammad Adnan Ramzani; Waqas-ud-Din Khan; Muhammad Iqbal; Salma Kausar; Shafaqat Ali; Muhammad Rizwan; Zaheer Abbas Virk (Environmental Science and Pollution Research, 2016)

Plant-driven removal of heavy metals from soil: uptake, translocation, tolerance mechanism, challenges, and future perspectives - Sveta Thakur; Lakhveer Singh; Zularisam Ab Wahid; Muhammad Faisal Siddiqui; Samson Mekbib Atnaw; Mohd Fadhil Md Din (Environmental Monitoring and Assessment, 2016)

Risk factors associated with Mycobacterium bovis skin positivity in cattle and buffalo in Peshawar, Pakistan - Irfan Khattak; Muhammad Hassan Mushtaq; Mansur ud Din Ahmad; Muhammad Sarwar Khan; Mamoona chaudhry; Umer Sadique (Tropical Animal Health and Production, 2016)

Organic amendments impact the availability of heavy metal(loid)s in mine-impacted soil and their phytoremediation by Penisitum americanum and Sorghum bicolor - Javed Nawab; Sardar Khan; Muhammad Aamir; Isha Shamshad; Zahir Qamar; Islamud Din; Qing Huang (Environmental Science and Pollution Research, 2016)

An overview of phytochrome: An important light switch and photo-sensory antenna for regulation of vital functioning of plants - Abdul Qayyum Rao; Muhammad Azmat Ullah Khan; Naila Shahid; Salah ud Din; Ambreen Gul; Adnan Muzaffar; Saira Azam; Tahir Rehman Samiullah; Fatima Batool; Ahmad Ali Shahid; Idrees Ahmad Nasir; Tayyab Husnain (Biologia, 2015)

Mutation of ATF6 causes autosomal recessive achromatopsia - Muhammad Ansar; Regie Lyn P. Santos-Cortez; Muhammad Arif Nadeem Saqib; Fareeha Zulfiqar; Kwanghyuk Lee; Naeem Mahmood Ashraf; Ehsan Ullah; Xin Wang; Sundus Sajid; Falak Sher Khan; Muhammad Amin-ud-Din; Joshua D. Smith; et al. (Human Genetics, 2015)

Synthesis, characterization and urease inhibition, in vitro anticancer and antileishmanial studies of Ni(II) complexes with N,N,N′-trisubstituted thioureas - Muhammad Khawar Rauf; Samad Yaseen; Amin Badshah; Sumera Zaib; Raffia Arshad; Imtiaz-ud-Din; Muhammad Nawaz Tahir; Jamshed Iqbal (JBIC Journal of Biological Inorganic Chemistry, 2015)

Piercing and incubation method of in planta transformation producing stable transgenic plants by overexpressing DREB1A gene in tomato (Solanum lycopersicum Mill.) - Sabir Hussain Shah; Shaukat Ali; Sohail Ahmad Jan; Jalal-Ud-Din; Ghulam Muhammad Ali (Plant Cell, Tissue and Organ Culture (PCTOC), 2015)

Profiling and characterization of eggplant (Solanum melongena L.) microRNAs and their targets - Muhammad Din; Muhammad Younas Khan Barozai (Molecular Biology Reports, 2014)

Investigation of equine influenza virus in two geographical regions of Pakistan - Muhammad Sajid; Mansur-ud-Din Ahmad; Muhammad Athar Khan; Muhammad Aftab Anjum; Muhammad Hassan Mushtaq (Tropical Animal Health and Production, 2013)

Identification of MicroRNAs and their targets in Helianthus - Muhammad Younas Khan Barozai; Iftikhar Ahmed Baloch; Muhammad Din (Molecular Biology Reports, 2012)

Epidermal growth factor receptors: function modulation by phosphorylation and glycosylation interplay - Afshan Kaleem; Ishtiaq Ahmad; Daniel C. Hoessli; Evelyne Walker-Nasir; Muhammad Saleem; Abdul Rauf Shakoori; Nasir-ud-Din (Molecular Biology Reports, 2009)

Evolutionary history of the somatostatin and somatostatin receptors - Muhammad Moaeen-Ud-Din; Li Guo Yang (Journal of Genetics, 2009)

Novel mutations in G protein-coupled receptor gene (P2RY5) in families with autosomal recessive hypotrichosis (LAH3) - Zahid Azeem; Musharraf Jelani; Gul Naz; Muhammad Tariq; Naveed Wasif; Syed Kamran-ul-Hassan Naqvi; Muhammad Ayub; Masoom Yasinzai; Muhammad Amin-ud-din; Abdul Wali; Ghazanfar Ali; Muhammad Salman Chishti; et al. (Human Genetics, 2008)